Adaptive Variation Amid High Gene Flow Across a Broad Latitudinal Gradient in the Reef‐Building Honeycomb Worm, Sabellaria alveolata - Edward J. Wilson; Antony M. Knights; Louise B. Firth; Charlotte Corporeau; Amelia Curd; Stanislas F. Dubois; Fernando P. Lima; Rui Seabra; Flavia L. D. Nunes (Molecular Ecology, 2026)
Climate change is already altering, and will continue to reshape, the persistence and spatial structure of marine populations. Understanding metapopulation connectivity and local adaptation is therefore critical for identifying both vulnerable populations and those with adaptive resilience. We applied a seascape genomics approach to investigate connectivity patterns and adaptive responses in the honeycomb worm, Sabellaria alveolata —an intertidal ecosystem engineer that supports high biodiversity and provides essential ecological functions. A total of 286 individuals from 17 sites spanning the entire latitudinal range were genotyped to assess population structure and local adaptation. Outlier analyses (BayeScan and OutFlank) identified six adaptive and 2117 neutral SNPs. Neutral SNP analysis revealed low to moderate genetic differentiation, indicating well‐connected populations. Admixture with possible ancestral gene pools in Southern Edge and Biscay populations suggests the persistence of unique genetic diversity. While connectivity is likely driven by natural larval dispersal, human‐mediated transport resulting from support vessels, aquaculture, marine debris and expanding offshore and coastal infrastructure may also facilitate gene flow, shaping observed genetic patterns. Despite this high connectivity, we detected genetic signatures of adaptation to temperature, salinity and net primary productivity, with adaptive SNPs linked to genes involved in molecular and physiological responses to these environmental factors. Our findings suggest that S. alveolata is likely resilient to climate change and other anthropogenic pressures, making it a valuable model for investigating the genetic and physiological underpinnings of marine population resilience.

The Impact of Pulp Mill Closures on Pine Plantation Investment Returns in the US South - Bruno Kanieski da Silva; Mateus N. I. Sanquetta; Hannah Knight; Stephen M. Kinane; Erin Lincoln; Jacek Siry; Yanshu Li (Journal of Forestry, 2026)
Pulp and paper mill closures have had a significant impact on the forest sector in the southeastern US over the last decade. These mills consume large volumes of pulpwood, and a complete shutdown of their operations has potential to significantly reduce pulpwood prices. In this study, we investigated the effects of pine pulpwood stumpage prices on financial returns in four different timber markets in the southeastern US (northeast and northwest Florida, south Georgia and east South Carolina). Through simulations of two stand densities (300 and 600 trees per acre), three thinning treatments (no-thinning, one and two thinnings), we assessed the Land Expectation Value (LEV) under scenarios of 50% and 100% reductions of pulpwood prices. In addition, through an optimization model, we estimated the changes on the stumpage prices of pine chip-n-saw and sawtimber required to offset the losses with pulpwood market. Our results indicated that although lower pulpwood prices decrease timberland investment returns, some silvicultural strategies, like thinning trees less often and planting fewer trees per acre, will suffer lower financial losses. Also, although chip-n-saw and sawtimber prices might compensate for lower pulpwood demand, it is unlikely that we will observe higher stumpage prices of any product in the near future. Our results indicate that landowners should develop adaptive strategies to ensure the economic viability of timberland investments and face these market shifts.

Safe harbours for the intruders of the sea: Greater abundance of invasive species on artificial structures and management implications - Laura Avila-Turriago; Jasmine B.D. Jaffrés; Michael Sievers; Brigette Wright; Ariane Easton; Louise B. Firth; Antony M. Knights; Niclas Einert; Tom Coughlin; Naomi Forrest; Sven Frijlink; Valeriya Komyakova (Global Environmental Change, 2026)

Variation in systemic biological health risk is associated with white matter integrity differences in young adult veterans - Emily J. Van Etten; Madeleine K. Nowak; Caitlin M. Bolduc; Shira Hao; Arielle R. Knight; Aubrey A. Knoff; William P. Milberg; Catherine B. Fortier; David H. Salat (Brain Imaging and Behavior, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sector expert and public perceptions of greening of grey infrastructure: a case study in Britain’s Ocean City - Jessica R. Allen; Anaëlle J. Lemasson; Melanie J. Bishop; Katherine A. Dafforn; Kate C. Dodds; Mick E. Hanley; Antony M. Knights; Mariana Mayer-Pinto; Abigail McQuatters-Gollop; Maria L. Vozzo; Louise B. Firth (Urban Ecosystems, 2026)

Population genetic structure and patterns of hybridization of the rare Lupinus tidestromii and its congener L. chamissonis (Fabaceae) inform seed sourcing strategies for population augmentation and reintroduction - Aspen Workman; Eleanor A. Pardini; Lorraine S. Parsons; Stefan G. Michalski; Tiffany M. Knight; Walter Durka (Conservation Genetics, 2026)
Human activities can impact the genetic diversity of populations, making them more vulnerable to extinction. Rare species are at an increased risk of negative genetic consequences of human activities, but understanding genetic diversity in rare species requires comparison to more common congeners. Hybridization, a common phenomenon in plants, can provide genetic rescue of genetically depauperate populations or put rare species at risk of being “swamped” out of the population. Human-mediated dispersal can create novel sympatry between previously allopatric species, fostering hybridization. The endangered Tideström’s lupine ( Lupinus tidestromii Greene ), endemic to the coastal dune ecosystem of California, co-occurs and hybridizes with the more common dune bush lupine ( L. chamissonis Eschsch .). We characterized 532 individuals from sympatric and non-sympatric sites across both species’ entire geographic ranges using genotyping-by-sequencing technology to identify 1,377 single-nucleotide polymorphisms. We analyzed population structure, genetic diversity within and among populations, and hybridization between L. tidestromii and L. chamissonis . Genetic diversity was lower in L. tidestromii than in the more common L. chamissonis . Both species showed strong population structure which coincided with a deep intraspecific split between populations north and south of San Francisco. Hybridization was confirmed at all sites of co-occurrence. Evidence of hybridization at multiple non-sympatric sites indicated former co-occurrence and recent local extirpations. From these results, we make specific management recommendations for L. tidestromii . Seeds from large populations in the north can be used to augment the smaller populations in this region and to reintroduce this endangered species back to extirpated sites. Our results highlight how studies considering spatial patterns of genetic diversity, hybridization and private alleles can be used to make clear recommendations for conservation actions.

Topographic and biogenic complexity drive the spatio-temporal formation of microclimate on intertidal eco-engineered seawalls - Franz Bauer; Louise B. Firth; Antony M. Knights; John N. Griffin; Andy Foggo; Austin Brown; Mick E. Hanley (Marine Pollution Bulletin, 2026)

Wave overtopping on eco-engineered seawalls: Does biodiversity enhancement conflict with coastal protection? - Franz Bauer; Antony M. Knights; Louise B. Firth; John N. Griffin; Andy Foggo; Austin Brown; Martyn Hann; David Simmonds; Mick E. Hanley (Journal of Environmental Management, 2026)

Considerations on the process of target selection for the Comet Interceptor mission - C. Snodgrass; E. Mazzotta Epifani; C. Tubiana; J.P. Sánchez; N. Biver; L. Inno; M.M. Knight; P. Lacerda; J. De Keyser; A. Donaldson; N.J.T. Edberg; M. Galand; et al. (Icarus, 2026)

Reusable plastic crates vs. wooden crates: Comparing microbial contamination and costs during long-distance transportation of tomatoes in Ethiopia - Biruk Alemu Gemeda; Kebede Amenu; Claudia Ganser; Coen P.A. van Wagenberg; Sisay Girma; Wubetu Bihon; Ramasamy Srinivasan; Degaga Guder; Abdallahi Abdurehman; Eyob Gelan; Loretta M. Friedlich; Michelle D. Danyluk; et al. (Food Control, 2026)

Herbarium Specimens Reveal Long‐Term Decline in Pollination Services Since the 1970s - Bofeng Song; Heidi Zimmer; Mark Clements; Demetra Rakosy; Tiffany M. Knight; Joanne M. Bennett (Global Change Biology, 2026)
Anthropogenic change has resulted in pollinator declines and altered plant–pollinator interactions. This may alter pollination services, reducing the reproductive success of plants. Yet few datasets allow us to track changes in pollination services over time. Herbaria provide a unique opportunity to assess pollination services across broad spatial and temporal scales enabling the examination of associated spatiotemporal anthropogenic drivers of change. We quantified changes in pollination services to the orchid genus Caladenia over the past century, a period of rapid land‐use intensification and climate change in Australia. Examining 10,494 Caladenia flowers preserved at the Australian National Herbarium showed a reduction in pollination services totaling > 60% over the whole study period, with rapid declines occurring post 1970. Declines in pollination services occurred across species pollinated by different taxa and with varying threat status. Sexually deceptive species showed more pronounced declines in pollination services than food‐deceptive species, whereas no decline was detected in the self‐compatible species. Land‐use intensity and rising temperatures were significant predictors of changes in pollination service. Our findings provide rare evidence of declines in pollination services and demonstrate the value of herbarium collections in understanding global change.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Select genotypes of white and green ash show heritable, elevated resistance to emerald ash borer - Mary E. Mason; Dave W. Carey; Jeanne Romero-Severson; Kathleen S. Knight; Therese M. Poland; Jennifer L. Koch (New Forests, 2026)

Assessment of the movement behaviour of dusky kob Argyrosomus japonicus along the coast of South Africa using 39 years of tag-recapture data from a voluntary tagging project - T Knight; M Farthing; A Winkler; BQ Mann; A-R Childs; WM Potts (African Journal of Marine Science, 2025)

The interaction of financial incentives and social norms to motivate conservation on the Tibetan Plateau - John M. Kerr; Tsering Bum; Rain Wuyu Liu; Jinhua Zhao; Lu Zhi; Maria Knight Lapinski (Ecosystem Services, 2025)

Pre-adult political experiences and political participation - Sylvia Knight; David A. M. Peterson (The Social Science Journal, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

Petrogenesis of the olivine cumulate outcrop Issole – The missing link between the Séítah and Máaz formations in Jezero crater, Mars - Juan David Hernández-Montenegro; Tanya V. Kizovski; Allan H. Treiman; An Y. Li; Paul D. Asimow; Mariek E. Schmidt; Yang Liu; Josh Labrie; Abigail L. Knight; Michael M. Tice; David A. Klevang; Scott VanBommel; et al. (Icarus, 2025)

Habitat selection as a reduction in habitat variance - Jenna Knight; James A. Schaefer; Brent R. Patterson; Stephen Sucharzewski; Joseph M. Northrup (Acta Oecologica, 2025)

Temperature-induced metabolic performance in early life stages of two brachyuran crabs - Kerry-Ann van der Walt; Seshnee Reddy; Antony M. Knights; Louise B. Firth; Francesca Porri (Journal of Thermal Biology, 2025)

Women's tenure security on collective lands: A conceptual framework - Ruth Meinzen-Dick; Cheryl Doss; Fiona Flintan; Rachael Knight; Anne M. Larson; Iliana Monterroso (Journal of Rural Studies, 2025)

Predicting the future distribution of a commercially important clam (Ruditapes philippinarum) in a changing climate - Alexandra S. Johnson; Amelia E.H. Bridges; Antony M. Knights (Estuarine, Coastal and Shelf Science, 2025)

Scaling up eco-engineering: The role of topographic complexity and spatial variability in shaping biodiversity on coastal structures - Charlotte H. Clubley; Antony M. Knights; Jessica Allen; David T. Bilton; Andy Foggo; Mick E. Hanley; James Murphy; Louisa E. Wood; Louise B. Firth (Science of The Total Environment, 2025)

Metabolic Diversity of a Widely Distributed Tropical Freshwater Crab Is Not Underpinned by Genetic Differences - Lucy M. Turner; Christopher J. Thorpe; Michael Collins; Smrithy Raj; Tripti Shukla; John I. Spicer; Mairi E. Knight; Dheeraj Sharma; Krushnamegh Kunte (Journal of Biogeography, 2025)
Aim The aim of this study was to understand the interplay between local and regional factors as drivers of population physiological diversity in a tropical freshwater crab species. Location Western Ghats, south‐west India. Taxon Barytelphusa cunicularis, Brachyura, Crustacea. Methods We applied an integrative approach combining population genetics and whole animal physiology, using the tropical freshwater crab Barytelphusa cunicularis as our model species. We tested for effects of population location (e.g., latitude, altitude), season (as a proxy for rainfall and water temperature) and/or warming on indices of whole animal respiratory physiology (metabolic rate, MO 2 ) and hypoxic performance (P crit , i.e., the PO 2 at which routine MO 2 can no longer be sustained) in five widely distributed populations of this species. We also generated population genetic data (mtDNA COI and nDNA histone H3 sequences) to determine the extent of any population genetic structuring and/or cryptic species diversity present to verify that we were investigating a single species. Results Despite a high level of genetic structuring between the different populations of B. cunicularis examined, the genetic distances observed were consistent with intra‐ and not interspecific differences in freshwater crabs. Populations varied in the diversity of the physiological (MO 2 ) responses observed. There were significant effects of season and population on respiration in response to temperature and P crit in response to acute hypoxia. Main Conclusions We conclude that local environmental factors are important in shaping physiological diversity between populations in tropical freshwater species and systems. This highlights the need to include population‐level responses in any projections we make on how biodiversity will respond to ongoing and future environmental changes, including those caused by climate change.

Cruel Summer (and Autumn): Humid Heat Trends, Extremes, and Mechanisms in the Southeast United States - Shawn M. Milrad; Kelsey E. Ennis; Desiree A. Knight; Kathie D. Dello; Lily Raye; Kyle R. Wodzicki (International Journal of Climatology, 2025)
Humid heat has increased in frequency, intensity and duration in many locations across the globe, particularly those with warm and moist climates like much of the Southeast United States. This study employs an established wet bulb globe temperature (WBGT) estimation formula and high‐resolution reanalysis data to develop a custom gridded WBGT dataset for the Southeast. Subsequently, summer and autumn WBGT (humid heat) trends and extremes are elucidated for 1950–2023. Results complement and correspond well to recent station‐based work as well as gridded trends in the Universal Thermal Comfort Index (UTCI). Overall, trends in average and extreme (90th percentile) WBGT are larger and more widely statistically significant at night and during summer. Autumn WBGT increases are largest and most significant in the Florida Peninsula and near the Gulf Coast, where the heat content of the adjacent water peaks in September. Furthermore, there are large increases in the frequency and duration of summer night‐time extremes; regions near the Gulf and in Florida are experiencing nearly three additional extreme summer nights per decade, and extreme events are approximately one night longer per decade. A quantification of WBGT components shows that moisture (dewpoint) increases exceed temperature increases and are the largest contributors to WBGT across most of the Southeast, except in parts of the Appalachian and Piedmont regions where temperature changes dominate. Wind speed and solar radiation changes are quite small across the Southeast and are at best minor contributors to WBGT trends. Results support previous literature that moisture changes are most responsible for humid heat trends in warm and moist climates.

Correction: The IGCP 714 Project “3GEO– Geoclimbing & Geotrekking in Geoparks”– Selection of Geodiversity Sites Equipped for Climbing for Combining Outdoor and Multimedia Activities - Irene Maria Bollati; Anna Masseroli; Mohammed Al Kindi; Lucas Cezar; Anna Chrobak-Žuffová; Ashish Dongre; Charalampos Fassoulas; Eugenio Fazio; Manuel Garcia-Rodríguez; Jasper Knight; Jack J. Matthews; Ricardo Galeno Fraga de Araújo Pereira; et al. (Geoheritage, 2025)

Thermal patterns on eco-engineered coastal infrastructure depend on topographic complexity and spatial scale - Franz Bauer; Antony M. Knights; Mick E. Hanley; John N. Griffin; Andy Foggo; Austin Brown; Melanie J. Bishop; Katherine A. Dafforn; Mariana Mayer-Pinto; Louise B. Firth (Ecological Engineering, 2025)

Restricted cirque glaciers in the Wicklow Mountains, Ireland, during the Nahanagan Stadial (Greenland Stadial‐1/Younger Dryas) - Lauren Knight; Clare M. Boston; Harold Lovell; Timothy T. Barrows; Eric A. Colhoun; David Fink; Nicholas C. Pepin (Journal of Quaternary Science, 2025)
In Ireland, the Nahanagan Stadial (NS) was characterised by cirque glacier, plateau icefield and mountain ice cap expansion and is named after the cirque glacier type‐site of Lough Nahanagan in the Wicklow Mountains. This period is broadly equivalent to the Younger Dryas Stadial and Greenland Stadial‐1 (GS‐1: ~12.9–11.7 ka). Here, we provide the first evaluation of the full extent of NS glaciation in the Wicklow Mountains by combining solar radiation modelling, mapping of glacial geomorphology, 10 Be and 26 Al cosmogenic surface exposure dating, 3D glacier reconstructions and analysis of snowblow and avalanching potential. We identify seven sites that hosted cirque glaciers at this time. Glacier extent was very restricted, with most glaciers only partially filling their cirques. Equilibrium line altitudes (ELAs) ranged from 470 ± 5 m a.s.l. (Lough Nahanagan) to 721 ± 5 m a.s.l. (Lough Cleevaun), with an average ELA of 599 m a.s.l. Higher snowblow and avalanching contributions at sites with lower ELAs demonstrate local topoclimatic influence on glacier growth and preservation alongside regional climate. The Wicklow Mountains provides a good example of marginal cirque glaciation during GS‐1 and the importance of local topography and microclimate for sustaining glaciers in some mountain areas of Britain and Ireland.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Diet and landscape controls on greenhouse gas emissions from cattle excreta in a semi-arid environment - Jiancan Liu; J. Diane Knight; Reynald L. Lemke; Helen M. Baulch; Richard E. Farrell (Agriculture, Ecosystems & Environment, 2025)

Cost-effectiveness of interventions toward improving microbial food safety of chicken meat along supply chains in Burkina Faso and Ethiopia - James Noah Ssemanda; Heidy M.W. den Besten; Michel M. Dione; Kebede Amenu; Theodore J.D. Knight-Jones; Marcel H. Zwietering; Coen P.A. van Wagenberg (International Journal of Food Microbiology, 2025)

The role of limpets in biodiversity patterns and bioerosion on coastal infrastructure: Insights from Plymouth Breakwater - Aeden Cooper; Antony M. Knights; Sandalia Walker; Juan Sempere-Valverde; Chris Moocarme; Stephen J. Hawkins; Louise B. Firth (Ecological Engineering, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Effect of resolution on simulated teleconnections to winter North Atlantic circulation inferred from a causal network derived from expert elicitation - David M. H. Sexton; Kuniko Yamazaki; John W. Rostron; Nick J. Dunstone; David R. Fereday; Steven C. Hardiman; Sarah Ineson; Jeff R. Knight (Climate Dynamics, 2025)

Why Is It Too Cold? Towards a Mechanistic Understanding of Cold‐Water Pollution Effects on Recruitment of an Imperiled Warmwater Fish - Eliza I. Gilbert; Tracy A. Diver; Steven M. Mussmann; Melody J. Saltzgiver; William K. Knight; Scott L. Durst; Michael A. Farrington; Stephani L. Clark Barkalow; Michael Tobler; Nathan R. Franssen (Molecular Ecology, 2025)
Environmental temperature shapes the ontogeny of ectotherms by influencing rates of growth and development which can be key determinants of survival. Whereas the escalating impacts of water management on freshwater ecosystems is well documented, the effects of cold‐water releases from dams—which can alter downstream temperatures—remains relatively underexplored but may present novel challenges to endemic ectotherms. Specifically, little is known about how thermal depressions reshape phenotypic and genetic patterns during larval metamorphosis for fishes that evolved in warmwater systems. We assessed the effects of thermal shifts on larval ontogeny of the endangered razorback sucker ( Xyrauchen texanus ), which evolved in the warm waters of the Colorado River Basin, USA. We hypothesised that development is more sensitive to cold‐water influences than growth and that temperature would influence patterns in gene expression related to development. Our results supported these hypotheses and showed that both wild and laboratory‐reared larvae in slightly cooler temperatures exhibited delayed development, but similar growth compared to larvae reared in warmer conditions. These findings suggest growth and development in early ectotherm life stages can be decoupled, which follows patterns more like the temperature‐size rule than allometric scaling of development by size. We also observed transcriptional differences related to genes associated with stress responses and development in our laboratory‐reared fish; here, gene expression of fish from the coldest conditions at the end of the experiment was more similar to fish reared in warmer temperatures at the midpoint. Our findings suggest that modest temperature reductions can delay ontogeny and alter the transcriptional landscape while not necessarily limiting growth. This finding highlights the need for conservation practitioners to consider cascading impacts that even small temperature reductions can cause in riverine ecosystems.

Sex-specific variation in species interactions matters in ecological communities - Elena Gissi; Maurice Codespoti Goodman; Robin Elahi; Jamie M. McDevitt-Irwin; Natalie S. Arnoldi; Nur Arafeh-Dalmau; Christopher J. Knight; Carolina Olguín-Jacobson; Melissa Palmisciano; Ceyenna M. Tillman; Giulio A. De Leo; Fiorenza Micheli (Trends in Ecology & Evolution, 2024)

Ecosystem engineers enhance the multifunctionality of an urban novel ecosystem: Population persistence and ecosystem resilience since the 1980s - Louise B. Firth; Anastasia Forbes; Antony M. Knights; Kathryn A. O'Shaughnessy; Wahaj Mahmood-Brown; Lewis Struthers; Ellie Hawcutt; Katrin Bohn; Martin D.J. Sayer; James Quinn; Jan Allen; Simone Dürr; et al. (Science of The Total Environment, 2024)

Multi-generational dispersal and dynamic patch occupancy reveals spatial and temporal stability of seascapes - Charlotte H. Clubley; Tiago A.M. Silva; Louisa E. Wood; Louise B. Firth; David T. Bilton; Enda O'Dea; Antony M. Knights (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Effect of sodium lignosulfonate and propionic acid application rate on dry matter losses, nutritional composition, in vitro gas production, and fungal populations of high moisture alfalfa hay mini bales - Marjorie A. Killerby; Saulo T.R. Almeida; Godloves M. Oppong; Diego Zamudio; Colt Knight; Lewis B. Perkins; Changqing Wu; Seanna Annis; Juan J. Romero (Animal Feed Science and Technology, 2024)

The IGCP 714 Project “3GEO – Geoclimbing & Geotrekking in Geoparks” – Selection of Geodiversity Sites Equipped for Climbing for Combining Outdoor and Multimedia Activities - Irene Maria Bollati; Anna Masseroli; Mohammed Al Kindi; Lucas Cezar; Anna Chrobak-Žuffová; Ashish Dongre; Charalampos Fassoulas; Eugenio Fazio; Manuel Garcia-Rodríguez; Jasper Knight; Jack J. Matthews; Ricardo Galeno Fraga de Araújo Pereira; et al. (Geoheritage, 2024)
The IGCP 714 project “3GEO – Geoclimbing & Geotrekking in Geoparks ” is financed by the International Geoscience Programme (IGCP) and supported by the International Union of Geological Sciences (IUGS). In this paper, we report on the results of the first phase of the project focused on the criteria to be adopted to select geodiversity sites equipped for climbing or trekking. The selection of geoclimbing sites and geotrekking routes is aimed at combining multimedia tools and outdoor activities for Geosciences promotion and conservation in UNESCO Global Geoparks, aspiring geoparks or geoparks project, and also in protected areas featuring geoheritage sites. Indeed, both outdoor activities and multimedia tools favour the pursuing of many of the United Nations Sustainable Development Goals (e.g., 3, 4, 8, 11). An international consortium of geoscientists from 12 different countries selected, through the proposed procedure, 22 geoclimbing sites, and then they also detected 30 geotrekking routes mirroring Earth geodiversity. At some test sites (geoclimbing and geotrekking) multimedia tools and digital outcrop models have been developed through different methodological approaches (e.g., Structure from Motion and Multi-View Stereo photogrammetry), to open the way to the second part of the project still in progress. These sites and the relative virtual models are herein also shown. The final aim of the IGCP 714 project is indeed to create an open data repository (digital outcrop models, videos, virtual tours, photos, scientific information, and interpretations) to upload data of the selected sites to mirror Earth geodiversity for different users including tourists and school groups.

The thermal expansion of Ti-substituted CaAl12O19 - Paul F. Schofield; Andrew J. Berry; Patricia M. Doyle; Kevin S. Knight (Physics and Chemistry of Minerals, 2024)
CaAl 12 O 19 , which can incorporate Ti as both Ti 3+ and Ti 4+ (charge coupled substitution with Mg 2+ ), is one of the first minerals to condense from a gas of solar composition and is used as a ceramic. It is variously known as hibonite, calcium hexaluminate (CaO.6Al 2 O 3 ), and CA 6 . The lattice parameters and unit cell volumes of Ti-substituted hibonite ( P 6 3 / mmc ) with the formulae CaAl 11.8 Ti 3+ 0.2 O 19 and CaAl 9.8 Ti 3+ 0.54 Mg 0.83 Ti 4+ 0.83 O 19 were determined as a function of temperature from ~ 10 to 275 K by neutron powder diffraction. The thermal expansion is highly anisotropic with the expansion in c a factor of ~ 5 greater than that in a . The change in a is approximately equal for the two compounds whereas the change in c is almost 50% larger for CaAl 11.8 Ti 3+ 0.2 O 19 . CaAl 11.8 Ti 3+ 0.2 O 19 also exhibits negative thermal expansion between 10 and 70 K. The change in unit cell volume with temperature of both compositions is well described by a two term Einstein expression. The large change in c is consistent with substitution of Ti onto the M2 and M4 sites of the R-block structural unit.

Scale-dependent topographic complexity underpins abundance and spatial distribution of ecosystem engineers on natural and artificial structures - Franz Bauer; Antony M. Knights; John N. Griffin; Mick E. Hanley; Andy Foggo; Austin Brown; Emma Jones; Louise B. Firth (Science of The Total Environment, 2024)

Intelligent control of combined sewer systems using PySWMM—A Python wrapper for EPA’s Stormwater Management Model - M.E. Tryby; C.A. Buahin; B.E. McDonnell; W.J. Knight; J. Fortin-Flefil; M. VanDoren; S. Eckenwiler; H. Boyer (Environmental Modelling & Software, 2024)

Career Paths of Doctoral Recipients in Engineering and Computer Science: Trends by Sex, Race, Citizenship, and Discipline with an Emphasis on Biomedical Engineering - Maya Denton; David B. Knight; Jessica R. Deters; Dustin M. Grote; Maura Borrego (Biomedical Engineering Education, 2024)
We summarize national-scale data for Ph.D. earners in engineering or computer science from 2015 to 2019 whose post-graduate school employment is known, highlighting outcomes for biological/biomedical/biosystems engineering students. We use NSF’s Survey of Earned Doctorates (SED), which has collected information from Ph.D. recipients in the USA since 1957. The data are collected at the time of degree completion and constitute a greater than 90% response rate. Compared to all engineering and computer science disciplines, biological/biomedical/biosystems engineering has a higher proportion going to 4yr/med/research institutions (52% vs. 33%) and non-profit (3.6% vs. 2.9%) and lower proportion going to industry (33% vs. 48%), government (4.3% vs. 8.4%), and is similar for non-US positions (6.1% vs. 5.7%). Compared to 2010–2014 biological/biomedical/biosystems engineering Ph.D. recipients, more 2015–2019 recipients are going to industry (25% to 33%) and fewer to 4yr/med/research institutions (59% to 52%) and governmet (5.3% to 4.3%). Across all engineering and computer science disciplines, a smaller proportion of females entered industry (43%) compared to males (49%), while a larger proportion of females entered 4yr/med/research institutions (37%) compared to males (32%). Over half of Asian doctoral recipients entered industry, as compared to 38% of Hispanic doctoral recipients. In contrast, a higher proportion of Hispanic individuals (37%) entered 4yr/med/research institutions after their doctoral programs, as compared to 31% of Asian doctoral recipients. Black doctoral recipients had the highest proportion enter positions in government (14%) and non-profit (4%) sectors. Our results are situated in the broader literature focused on postdoctoral career, training, and employment sectors and trends in STEM. We discuss implications for graduate programs, policymakers, and researchers.

PhD Student Funding Patterns: Placing Biomedical, Biological, and Biosystems Engineering in the Context of Engineering Sub-disciplines, Biological Sciences, and Other STEM Disciplines - David B. Knight; Dustin M. Grote; Timothy J. Kinoshita; Maura Borrego (Biomedical Engineering Education, 2024)
Whether doctoral students are funded primarily by fellowships, research assistantships, or teaching assistantships impacts their degree completion, time to degree, learning outcomes, and short- and long-term career outcomes. Variations in funding patterns have been studied at the broad field level but not comparing engineering sub-disciplines. We addressed two research questions: How do PhD student funding mechanisms vary across engineering sub-disciplines? And how does variation in funding mechanisms across engineering sub-disciplines map onto the larger STEM disciplinary landscape? We analyzed 103,373 engineering and computing responses to the U.S. Survey of Earned Doctorates collected between 2007 and 2016. We conducted analysis of variance with Bonferroni post hoc comparisons to examine variation in funding across sub-disciplines. Then, we conducted a k-means cluster analysis on percentage variables for fellowship, research, and teaching assistantship funding mechanism with STEM sub-discipline as the unit of analysis. A statistically significantly greater percentage of biomedical/biological engineering doctoral students were funded via a fellowship, compared to every other engineering sub-discipline. Consequently, biomedical/biological engineering had significantly lower proportions of students supported via research and teaching assistantships than nearly all other engineering sub-disciplines. We identified five clusters. The majority of engineering sub-disciplines grouped together into a cluster with high research assistantships and low teaching assistantships. Biomedical/biological engineering clustered in the high fellowships grouping with most other biological sciences but no other engineering sub-disciplines. Biomedical/biological engineering behaves much more like biological and life sciences in utilizing fellowships to fund graduate students, far more than other engineering sub-disciplines. Our study provides further evidence of the prevalence of fellowships in life sciences and how it stretches into biomedical/biological engineering. The majority of engineering sub-disciplines relied more on research assistantships to fund graduate study. The lack of uniformity provides an opportunity to diversify student experiences during their graduate programs but also necessitates an awareness to the advantages and disadvantages that different funding portfolios can bestow on students.

Land use modulates resistance of grasslands against future climate and inter‐annual climate variability in a large field experiment - Lotte Korell; Martin Andrzejak; Sigrid Berger; Walter Durka; Sylvia Haider; Isabell Hensen; Yva Herion; Johannes Höfner; Liana Kindermann; Stefan Klotz; Tiffany M. Knight; Anja Linstädter; et al. (Global Change Biology, 2024)
Climate and land‐use change are key drivers of global change. Full‐factorial field experiments in which both drivers are manipulated are essential to understand and predict their potentially interactive effects on the structure and functioning of grassland ecosystems. Here, we present 8 years of data on grassland dynamics from the Global Change Experimental Facility in Central Germany. On large experimental plots, temperature and seasonal patterns of precipitation are manipulated by superimposing regional climate model projections onto background climate variability. Climate manipulation is factorially crossed with agricultural land‐use scenarios, including intensively used meadows and extensively used (i.e., low‐intensity) meadows and pastures. Inter‐annual variation of background climate during our study years was high, including three of the driest years on record for our region. The effects of this temporal variability far exceeded the effects of the experimentally imposed climate change on plant species diversity and productivity, especially in the intensively used grasslands sown with only a few grass cultivars. These changes in productivity and diversity in response to alterations in climate were due to immigrant species replacing the target forage cultivars. This shift from forage cultivars to immigrant species may impose additional economic costs in terms of a decreasing forage value and the need for more frequent management measures. In contrast, the extensively used grasslands showed weaker responses to both experimentally manipulated future climate and inter‐annual climate variability, suggesting that these diverse grasslands are more resistant to climate change than intensively used, species‐poor grasslands. We therefore conclude that a lower management intensity of agricultural grasslands, associated with a higher plant diversity, can stabilize primary productivity under climate change.

A Switch from Glial to Neuronal Gene Expression Alterations in the Spinal Cord of SIV-infected Macaques on Antiretroviral Therapy - Kathleen R. Mulka; Suzanne E. Queen; Lisa M. Mangus; Sarah E. Beck; Audrey C. Knight; Megan E. McCarron; Clarisse V. Solis; Arlon J. Wizzard; Jyotsna Jayaram; Carlo Colantuoni; Joseph L. Mankowski (Journal of Neuroimmune Pharmacology, 2024)

Topography-based modulation of environmental factors as a mechanism for intertidal microhabitat formation: A basis for marine ecological design - Franz Bauer; Antony M. Knights; Mick E. Hanley; John N. Griffin; Andy Foggo; Austin Brown; Louise B. Firth (Marine Pollution Bulletin, 2024)

Predicting plant–pollinator interactions: concepts, methods, and challenges - Guadalupe Peralta; Paul J. CaraDonna; Demetra Rakosy; Jochen Fründ; María P. Pascual Tudanca; Carsten F. Dormann; Laura A. Burkle; Christopher N. Kaiser-Bunbury; Tiffany M. Knight; Julian Resasco; Rachael Winfree; Nico Blüthgen; et al. (Trends in Ecology & Evolution, 2024)

The global impact of offshore wind farms on ecosystem services - Stephen C.L. Watson; Paul J. Somerfield; Anaëlle J. Lemasson; Antony M. Knights; Andrew Edwards-Jones; Joana Nunes; Christine Pascoe; Caroline Louise McNeill; Michaela Schratzberger; Murray S.A. Thompson; Elena Couce; Claire L. Szostek; et al. (Ocean & Coastal Management, 2024)

Complexity-functioning relationships differ across different environmental conditions - Mariana Mayer-Pinto; Amelia Caley; Antony M. Knights; Laura Airoldi; Melanie J. Bishop; Paul Brooks; Ricardo Coutinho; Tasman Crowe; Paolo Mancuso; Lais P.D. Naval-Xavier; Louise B. Firth; Rafael Menezes; et al. (Journal of Environmental Management, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Correction: Integrating shallow head measurements and InSAR data to quantify groundwater-storage change in San Joaquin Valley, California (USA) - M. Lees; R. Knight (Hydrogeology Journal, 2023)

Integrating shallow head measurements and InSAR data to quantify groundwater-storage change in San Joaquin Valley, California (USA) - M. Lees; R. Knight (Hydrogeology Journal, 2023)
Monitoring groundwater storage is essential for sustainable groundwater management. Storage can be quantified by considering the two main components through which storage change is expressed: saturation changes and deformation of aquifer materials. Here, these components were quantified using a selected area in California’s San Joaquin Valley (USA). First, this involved following existing observational approaches: quantifying the component expressed through saturation changes by identifying head measurements from shallow wells and scaling by specific yield. In the San Joaquin Valley, existing approaches to estimate the deformation component are to ignore it or approximate it with a simple linear relation to measured head. However, head and deformation measurements made at extensometers revealed that assuming a linear relationship between deformation and head might provide a poor estimate, particularly during periods in which measured head is rising. Instead, InSAR-derived surface deformation measurements were used to quantify the deformation component of storage changes. This showed that the two components—saturation and deformation—accounted for storage declines of equal magnitude over 2015–2021, suggesting that the deformation component should not be neglected when estimating storage changes in regions with subsidence. Summing the two calculated components gave a new estimate of the total storage change that captured the major trends seen in independent estimates, while better accounting for the deformation component. An additional benefit is that this method accounts for the deformation component in the unconfined aquifer. This method to quantify total storage change can be a practical and effective tool to support groundwater management.

Biophysical factors control invasive annual grass hot spots in the Mojave Desert - Tanner Corless Smith; Tara B. B. Bishop; Michael C. Duniway; Miguel L. Villarreal; Anna C. Knight; Seth M. Munson; Eric K. Waller; Ryan Jensen; Richard A. Gill (Biological Invasions, 2023)
Invasive annual grasses can promote ecosystem state changes and habitat loss in the American Southwest. Non-native annual grasses such as Bromus spp . a nd Schismus spp. have invaded the Mojave Desert and degraded habitat through increased fire occurrence, severity, and shifting plant community composition. Thus, it is important to identify and characterize the areas where persistent invasion has occurred, identifying where subsequent habitat degradation has increased. Previous plot and landscape-scale analyses have revealed anthropogenic and biophysical correlates with the establishment and dominance of invasive annual grasses in the Mojave Desert. However, these studies have been limited in spatial and temporal scales. Here we use Landsat imagery validated using an extensive network of plot data to map persistent and productive populations of invasive annual grass, called hot spots , across the entire Mojave Desert ecoregion over 12 years (2009–2020). We also identify important variables for predicting hot spot distribution using the Random Forest algorithm and identifying the most invaded subregions. We identified hot spots in over 5% of the Mojave Desert mostly on the western and eastern edges of the ecoregion, and invasive grasses were detected in over 90% of the Mojave Desert at least once in that time. Across the entire Mojave Desert, our results indicate that soil texture, aspect, winter precipitation, and elevation are the highest-ranking predictive variables of invasive grass hot spots , while anthropogenic variables contributed the least to the accuracy of the predictive model. The total area covered by hot spots varied significantly among subregions of the Mojave Desert. We found that anthropogenic variables became more important in explaining invasive annual establishment and persistence as spatial scale was reduced to the subregional level. Our findings have important implications for informing where land management actions can prioritize reducing invasive annual persistence and promoting restoration efforts.

Metrics matter: Multiple diversity metrics at different spatial scales are needed to understand species diversity in urban environments - Kathryn A. O'Shaughnessy; Antony M. Knights; Stephen J. Hawkins; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Louise B. Firth (Science of The Total Environment, 2023)

Challenges of evidence-informed offshore decommissioning: an environmental perspective - Anaëlle J. Lemasson; Paul J. Somerfield; Michaela Schratzberger; Antony M. Knights (Trends in Ecology & Evolution, 2023)

Considerations for realistic atmospheric environments: An application to corrosion testing - R.M. Katona; A.W. Knight; M. Maguire; C.R. Bryan; R.F. Schaller (Science of The Total Environment, 2023)

Field evaluation of electrostatic precipitators for particulate matter mitigation in a manure-belt layer facility - Reyna M. Knight; Matthew J. Herkins; Jeb S. Hocter; Shannon R. Milliken; Lingying Zhao; Heping Zhu (Biosystems Engineering, 2023)

Development and optimisation of full-scale prototype electrostatic precipitators in a laboratory for particulate matter mitigation in poultryfacilities - Reyna M. Knight; Jeb S. Hocter; Shannon R. Milliken; Matthew J. Herkins; Lingying Zhao; Heping Zhu (Biosystems Engineering, 2023)

Demographic synthesis for global tree species conservation - Bettina Ohse; Aldo Compagnoni; Caroline E. Farrior; Sean M. McMahon; Roberto Salguero-Gómez; Nadja Rüger; Tiffany M. Knight (Trends in Ecology & Evolution, 2023)

Science paper or big data? Assessing invasion dynamics using observational data - Charlotte H. Clubley; Louise B. Firth; Louisa E. Wood; David T. Bilton; Tiago A.M. Silva; Antony M. Knights (Science of The Total Environment, 2023)

Abiotic conditions affect nectar properties and flower visitation in four herbaceous plant species - Carolin Plos; Niklas Stelbrink; Christine Römermann; Tiffany M. Knight; Isabell Hensen (Flora, 2023)

Epibionts provide their basibionts with associational resistance to predation but at a cost - Sam Downes; Louise B. Firth; Antony M. Knights (Marine Environmental Research, 2023)

Differential effects of ocean acidification and warming on biological functioning of a predator and prey species may alter future trophic interactions - Rebecca Greatorex; Antony M. Knights (Marine Environmental Research, 2023)

Alteration of oral microbiome composition in children living with pesticide-exposed farm workers - Ian B. Stanaway; James C. Wallace; Sungwoo Hong; Carly S. Wilder; Foad H. Green; Jesse Tsai; Misty Knight; Tomomi Workman; Eric M. Vigoren; Marissa N. Smith; William C. Griffith; Beti Thompson; et al. (International Journal of Hygiene and Environmental Health, 2023)

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

Characterization of the molecular mechanisms of silicon uptake in coccolithophores - Sarah Ratcliffe; Erin M. Meyer; Charlotte E. Walker; Michael Knight; Heather M. McNair; Paul G. Matson; Debora Iglesias‐Rodriguez; Mark Brzezinski; Gerald Langer; Aleksey Sadekov; Mervyn Greaves; Colin Brownlee; et al. (Environmental Microbiology, 2023)
Coccolithophores are an important group of calcifying marine phytoplankton. Although coccolithophores are not silicified, some species exhibit a requirement for Si in the calcification process. These species also possess a novel protein (SITL) that resembles the SIT family of Si transporters found in diatoms. However, the nature of Si transport in coccolithophores is not yet known, making it difficult to determine the wider role of Si in coccolithophore biology. Here, we show that coccolithophore SITLs act as Na + ‐coupled Si transporters when expressed in heterologous systems and exhibit similar characteristics to diatom SITs. We find that CbSITL from Coccolithus braarudii is transcriptionally regulated by Si availability and is expressed in environmental coccolithophore populations. However, the Si requirement of C. braarudii and other coccolithophores is very low, with transport rates of exogenous Si below the level of detection in sensitive assays of Si transport. As coccoliths contain only low levels of Si, we propose that Si acts to support the calcification process, rather than forming a structural component of the coccolith itself. Si is therefore acting as a micronutrient in coccolithophores and natural populations are only likely to experience Si limitation in circumstances where dissolved silicon (DSi) is depleted to extreme levels.

Assessment of runnelling as a form of mosquito control in saltmarsh: efficacy, environmental impacts and management - J. M. Knight; S. K. Marx; P. E. R. Dale (Wetlands Ecology and Management, 2022)

Oscillations of the circadian clock protein, BMAL-1, align to daily cycles of mechanical stimuli: a novel means to integrate biological time within predictive in vitro model systems - Hannah K. Heywood; Laurence Gardner; Martin M. Knight; David A. Lee (In vitro models, 2022)
Purpose In vivo, the circadian clock drives 24-h rhythms in human physiology. Isolated cells in vitro retain a functional clockwork but lack necessary timing cues resulting in the rapid loss of tissue-level circadian rhythms. This study tests the hypothesis that repeated daily mechanical stimulation acts as a timing cue for the circadian clockwork. The delineation and integration of circadian timing cues into predictive in vitro model systems, including organ-on-a-chip (OOAC) devices, represent a novel concept that introduces a key component of in vivo physiology into predictive in vitro model systems. Methods Quiescent bovine chondrocytes were entrained for 3 days by daily 12-h bouts of cyclic biaxial tensile strain (10%, 0.33 Hz, Flexcell) before sampling during free-running conditions. The core clock protein, BMAL-1, was quantified from normalised Western Blot signal intensity and the temporal oscillations characterised by Cosinor linear fit with 24-h period. Results Following entrainment, the cell-autonomous oscillations of the molecular clock protein, BMAL-1, exhibited circadian (24 h) periodicity ( p < 0.001) which aligned to the diurnal mechanical stimuli. A 6-h phase shift in the mechanical entrainment protocol resulted in an equivalent shift of the circadian clockwork. Thus, repeated daily mechanical stimuli synchronised circadian rhythmicity of chondrocytes in vitro. Conclusion This work demonstrates that daily mechanical stimulation can act as a timing cue that is sufficient to entrain the peripheral circadian clock in vitro. This discovery may be exploited to induce and sustain circadian physiology within into predictive in vitro model systems, including OOAC systems. Integration of the circadian clock within these systems will enhance their potential to accurately recapitulate human diurnal physiology and hence augment their predictive value as drug testing platforms and as realistic models of human (patho)physiology.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Evolution of Permeability in Sandstone During Confined Brazilian Testing - T. Hagengruber; M. M. Reda Taha; E. Rougier; E. E. Knight; J. C. Stormont (Rock Mechanics and Rock Engineering, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Timing and hydrological conditions associated with bigheaded carp movement past navigation dams on the upper Mississippi river - Jon M. Vallazza; Kyle J. Mosel; David M. Reineke; Ann L. Runstrom; James H. Larson; Brent C. Knights (Biological Invasions, 2021)

Bucking the trend of pollinator decline: the population genetics of a range expanding bumblebee - J. V. Huml; J. S. Ellis; K. Lloyd; C. M. Benefer; M. Kiernan; M. J. F. Brown; M. E. Knight (Evolutionary Ecology, 2021)

Automated conservation assessment of the orchid family with deep learning - Alexander Zizka; Daniele Silvestro; Pati Vitt; Tiffany M. Knight (Conservation Biology, 2021)
International Union for Conservation of Nature (IUCN) Red List assessments are essential for prioritizing conservation needs but are resource intensive and therefore available only for a fraction of global species richness. Automated conservation assessments based on digitally available geographic occurrence records can be a rapid alternative, but it is unclear how reliable these assessments are. We conducted automated conservation assessments for 13,910 species (47.3% of the known species in the family) of the diverse and globally distributed orchid family (Orchidaceae), for which most species (13,049) were previously unassessed by IUCN. We used a novel method based on a deep neural network (IUC‐NN). We identified 4,342 orchid species (31.2% of the evaluated species) as possibly threatened with extinction (equivalent to IUCN categories critically endangered [CR], endangered [EN], or vulnerable [VU]) and Madagascar, East Africa, Southeast Asia, and several oceanic islands as priority areas for orchid conservation. Orchidaceae provided a model with which to test the sensitivity of automated assessment methods to problems with data availability, data quality, and geographic sampling bias. The IUC‐NN identified possibly threatened species with an accuracy of 84.3%, with significantly lower geographic evaluation bias relative to the IUCN Red List and was robust even when data availability was low and there were geographic errors in the input data. Overall, our results demonstrate that automated assessments have an important role to play in identifying species at the greatest risk of extinction.

Lagged and dormant season climate better predict plant vital rates than climate during the growing season - Sanne M. Evers; Tiffany M. Knight; David W. Inouye; Tom E. X. Miller; Roberto Salguero‐Gómez; Amy M. Iler; Aldo Compagnoni (Global Change Biology, 2021)
Understanding the effects of climate on the vital rates (e.g., survival, development, reproduction) and dynamics of natural populations is a long‐standing quest in ecology, with ever‐increasing relevance in the face of climate change. However, linking climate drivers to demographic processes requires identifying the appropriate time windows during which climate influences vital rates. Researchers often do not have access to the long‐term data required to test a large number of windows, and are thus forced to make a priori choices. In this study, we first synthesize the literature to assess current a priori choices employed in studies performed on 104 plant species that link climate drivers with demographic responses. Second, we use a sliding‐window approach to investigate which combination of climate drivers and temporal window have the best predictive ability for vital rates of four perennial plant species that each have over a decade of demographic data ( Helianthella quinquenervis , Frasera speciosa , Cylindriopuntia imbricata , and Cryptantha flava ). Our literature review shows that most studies consider time windows in only the year preceding the measurement of the vital rate(s) of interest, and focus on annual or growing season temporal scales. In contrast, our sliding‐window analysis shows that in only four out of 13 vital rates the selected climate drivers have time windows that align with, or are similar to, the growing season. For many vital rates, the best window lagged more than 1 year and up to 4 years before the measurement of the vital rate. Our results demonstrate that for the vital rates of these four species, climate drivers that are lagged or outside of the growing season are the norm. Our study suggests that considering climatic predictors that fall outside of the most recent growing season will improve our understanding of how climate affects population dynamics.

Lock operations influence upstream passages of invasive and native fishes at a Mississippi River high-head dam - Andrea K. Fritts; Brent C. Knights; Jessica C. Stanton; Amanda S. Milde; Jon M. Vallazza; Marybeth K. Brey; Sara J. Tripp; Thomas E. Devine; Wesley Sleeper; James T. Lamer; Kyle J. Mosel (Biological Invasions, 2021)

Brain-predicted age difference score is related to specific cognitive functions: a multi-site replication analysis - Rory Boyle; Lee Jollans; Laura M. Rueda-Delgado; Rossella Rizzo; Görsev G. Yener; Jason P. McMorrow; Silvin P. Knight; Daniel Carey; Ian H. Robertson; Derya D. Emek-Savaş; Yaakov Stern; Rose Anne Kenny; et al. (Brain Imaging and Behavior, 2021)

A multiscale framework for disentangling the roles of evenness, density, and aggregation on diversity gradients - Daniel J. McGlinn; Thore Engel; Shane A. Blowes; Nicholas J. Gotelli; Tiffany M. Knight; Brian J. McGill; Nathan J. Sanders; Jonathan M. Chase (Ecology, 2021)
Disentangling the drivers of diversity gradients can be challenging. The Measurement of Biodiversity (MoB) framework decomposes scale‐dependent changes in species diversity into three components of community structure: species abundance distribution (SAD), total community abundance, and within‐species spatial aggregation. Here we extend MoB from categorical treatment comparisons to quantify variation along continuous geographic or environmental gradients. Our approach requires sites along a gradient, each consisting of georeferenced plots of abundance‐based species composition data. We demonstrate our method using a case study of ants sampled along an elevational gradient of 28 sites in a mixed deciduous forest of the Great Smoky Mountains National Park, USA. MoB analysis revealed that decreases in ant species richness along the elevational gradient were associated with decreasing evenness and total number of species, which counteracted the modest increase in richness associated with decreasing spatial aggregation along the gradient. Total community abundance had a negligible effect on richness at all but the finest spatial grains, SAD effects increased in importance with sampling effort, and the aggregation effect had the strongest effect at coarser spatial grains. These results do not support the more‐individuals hypothesis, but they are consistent with a hypothesis of stronger environmental filtering at coarser spatial grains. Our extension of MoB has the potential to elucidate how components of community structure contribute to changes in diversity along environmental gradients and should be useful for a variety of assemblage‐level data collected along gradients.

Seeing through the static: the temporal dimension of plant–animal mutualistic interactions - Paul J. CaraDonna; Laura A. Burkle; Benjamin Schwarz; Julian Resasco; Tiffany M. Knight; Gita Benadi; Nico Blüthgen; Carsten F. Dormann; Qiang Fang; Jochen Fründ; Benoit Gauzens; Christopher N. Kaiser‐Bunbury; et al. (Ecology Letters, 2021)
Most studies of plant–animal mutualistic networks have come from a temporally static perspective. This approach has revealed general patterns in network structure, but limits our ability to understand the ecological and evolutionary processes that shape these networks and to predict the consequences of natural and human‐driven disturbance on species interactions. We review the growing literature on temporal dynamics of plant–animal mutualistic networks including pollination, seed dispersal and ant defence mutualisms. We then discuss potential mechanisms underlying such variation in interactions, ranging from behavioural and physiological processes at the finest temporal scales to ecological and evolutionary processes at the broadest. We find that at the finest temporal scales (days, weeks, months) mutualistic interactions are highly dynamic, with considerable variation in network structure. At intermediate scales (years, decades), networks still exhibit high levels of temporal variation, but such variation appears to influence network properties only weakly. At the broadest temporal scales (many decades, centuries and beyond), continued shifts in interactions appear to reshape network structure, leading to dramatic community changes, including loss of species and function. Our review highlights the importance of considering the temporal dimension for understanding the ecology and evolution of complex webs of mutualistic interactions.

Ocean Acidification Mitigates the Negative Effects of Increased Sea Temperatures on the Biomineralization and Crystalline Ultrastructure of Mytilus - Antony M. Knights; Matthew J. Norton; Anaëlle J. Lemasson; Natasha Stephen (Frontiers in Marine Science, 2020)

Nonadditive effects among threats on rare plant species - Holly L. Bernardo; Rachel Goad; Pati Vitt; Tiffany M. Knight (Conservation Biology, 2020)
The current loss of biodiversity has put 50,000 plant species at an elevated risk of extinction worldwide. Conserving at‐risk species is often complicated by covariance or nonadditivity among threats, which makes it difficult to determine optimal management strategies. We sought to demographically quantify covariance and nonadditive effects of more threats on more rare plant species than ever attempted in a single analysis. We used 1082 population reports from 186 populations across 3 U.S. states of 27 rare, herbaceous plant species collected over 15 years by citizen scientists. We used a linear mixed‐effects model with 4 threats and their interactions as fixed predictors, species as a random predictor, and annual growth rates as the response. We found a significant 3‐way interaction on annual growth rates; rare plant population sizes were reduced by 46% during the time immediately after disturbance when populations were also browsed by deer ( Odocoileus virginianus ) and had high levels of encroachment by woody species. This nonadditive effect should be considered a major threat to the persistence of rare plant species. Our results highlight the need for comprehensive, multithreat assessments to determine optimal conservation actions.

Relationship between conservation biology and ecology shown through machine reading of 32,000 articles - Rogier E. Hintzen; Marina Papadopoulou; Ross Mounce; Cristina Banks‐Leite; Robert D. Holt; Morena Mills; Andrew T. Knight; Armand M. Leroi; James Rosindell (Conservation Biology, 2020)
Conservation biology was founded on the idea that efforts to save nature depend on a scientific understanding of how it works. It sought to apply ecological principles to conservation problems. We investigated whether the relationship between these fields has changed over time through machine reading the full texts of 32,000 research articles published in 16 ecology and conservation biology journals. We examined changes in research topics in both fields and how the fields have evolved from 2000 to 2014. As conservation biology matured, its focus shifted from ecology to social and political aspects of conservation. The 2 fields diverged and now occupy distinct niches in modern science. We hypothesize this pattern resulted from increasing recognition that social, economic, and political factors are critical for successful conservation and possibly from rising skepticism about the relevance of contemporary ecological theory to practical conservation.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Do differences in developmental mode shape the potential for local adaptation? - L. L. Jupe; D. T. Bilton; A. M. Knights (Ecology, 2020)
Future climate change is leading to the redistribution of life on Earth as species struggle to cope with rising temperatures. Local adaptation allows species to become locally optimized and persist despite environmental selection, but the extent to which this occurs in nature may be limited by dispersal and gene flow. Congeneric marine gastropod species ( Littorina littorea and L. saxatilis ) with markedly different developmental modes were collected from across a latitudinal thermal gradient to explore the prevalence of local adaptation to temperature. The acute response of metabolic rate (using oxygen consumption as a proxy) to up‐ramping and down‐ramping temperature regimes between 6°C and 36°C was quantified for five populations of each species. The highly dispersive L. littorea exhibited minimal evidence of local adaptation to the thermal gradient, with no change in thermal optimum ( T opt ) or thermal breadth ( T br ) and a decline in maximal performance ( max ) with increasing latitude. In contrast, the direct developing L. saxatilis displayed evidence of local optimization, although these varied idiosyncratically with latitude, suggesting a suite of selective pressures may be involved in shaping thermal physiology in this relatively sedentary species. Our results show that the biogeography of thermal traits can differ significantly between related species, and show that interpopulation differences in thermal performance do not necessarily follow simple patterns that may be predicted based on latitudinal changes in environmental temperatures. Further research is clearly required to understand the mechanisms that can lead to the emergence of local adaptation in marine systems better and allow improved predictions of species redistribution in response to climate change.

Oxytetracycline reduces inflammation and treponeme burden whereas vitamin D3 promotes β-defensin expression in bovine infectious digital dermatitis - Kaitlyn M. Watts; Priyoshi Lahiri; Rakel Arrazuria; Jeroen De Buck; Cameron G. Knight; Karin Orsel; Herman W. Barkema; Eduardo R. Cobo (Cell and Tissue Research, 2020)

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

We need more realistic climate change experiments for understanding ecosystems of the future - Lotte Korell; Harald Auge; Jonathan M. Chase; Stanley Harpole; Tiffany M. Knight (Global Change Biology, 2020)

Understanding plant communities of the future requires filling knowledge gaps - Lotte Korell; Harald Auge; Jonathan M. Chase; W. Stanley Harpole; Tiffany M. Knight (Global Change Biology, 2020)

Current climate, isolation and history drive global patterns of tree phylogenetic endemism - Brody Sandel; Patrick Weigelt; Holger Kreft; Gunnar Keppel; Masha T. van der Sande; Sam Levin; Stephen Smith; Dylan Craven; Tiffany M. Knight (Global Ecology and Biogeography, 2020)
Aim We mapped global patterns of tree phylogenetic endemism (PE) to identify hotspots and test hypotheses about possible drivers. Specifically, we tested hypotheses related to current climate, geographical characteristics and historical conditions and assessed their relative importance in shaping PE patterns. Location Global. Time period We used the present distribution of trees, and predictors covering conditions from the mid‐Miocene to present. Major taxa studied All seed‐bearing trees. Methods We compiled distributions for 58,542 tree species across 463 regions worldwide, matched these to a recent phylogeny of seed plants and calculated PE for each region. We used a suite of predictor variables describing current climate (e.g., mean annual temperature), geographical characteristics (e.g., isolation) and historical conditions (e.g., tree cover at the Last Glacial Maximum) in a spatial regression model to explain variation in PE. Results Tree PE was highest on islands, and was higher closer to the equator. All three groups of predictor variables contributed substantially to the PE pattern. Isolation and topographic heterogeneity promoted high PE, as did high current tree cover. Among mainland regions, temperature seasonality was strongly negatively related to PE, while mean annual temperature was positively related to PE on islands. Some relationships differed among the major floristic regions. For example, tree cover at the Last Glacial Maximum was a positive predictor of PE in the Palaeotropics, while tree cover at the Miocene was a negative predictor of PE in the Neotropics. Main conclusions Globally, PE can be explained by a combination of geographical, historical and current factors. Some geographical variables appear to be key predictors of PE. However, the impact of historic and current climate variables differs considerably among the major floristic regions, reflecting their unique histories. Hence, the current distribution of trees is the result of globally relevant geographical drivers and regional climatic histories.

Factors Influencing Adherence to Recommended Colorectal Cancer Surveillance: Experiences and Behaviors of Colorectal Cancer Survivors - Marvella E. Ford; Katherine R. Sterba; Kent Armeson; Angela M. Malek; Kendrea D. Knight; Jane Zapka (Journal of Cancer Education, 2019)

Effects in rats of adolescent exposure to cannabis smoke or THC on emotional behavior and cognitive function in adulthood - Adriaan W. Bruijnzeel; Parker Knight; Stefany Panunzio; Song Xue; Matthew M. Bruner; Shannon C. Wall; Marjory Pompilus; Marcelo Febo; Barry Setlow (Psychopharmacology, 2019)

Preferential Parasitism of Native Oyster Ostrea edulis Over Non-Native Magallana gigas by a Polydorid Worm - A. J. Lemasson; A. M. Knights (Estuaries and Coasts, 2019)

Population projection models for 14 alien plant species in the presence and absence of aboveground competition - Sam C. Levin; Raelene M. Crandall; Tiffany M. Knight (Ecology, 2019)
Plant population ecologists strive to understand how environmental drivers influence demographic vital rates and thus population dynamics. Hundreds of studies have collected demographic data and used matrix and/or integral projection models to quantify lifetime fitness and population dynamics of plants. However, most of these studies have focused on native plant species, and there is a need for more studies on alien plants. Further, few studies on alien plants have experimentally manipulated environmental drivers in order to understand the mechanisms that allow alien plant species to have positive population growth. A synthetic understanding of the population dynamics of alien plant species will only be achieved if ecologists collect demographic data on many plant species and environments and provide the demographic data and model structure in a data archive for future comparisons and meta‐analyses. Invasive alien species are a social, economic, and ecological issue that has become increasingly important in an increasingly globalized world. Researchers continue to forecast impacts and prevent new introductions by seeking a robust understanding of drivers of invasive species success and failure. Researchers have hypothesized that competitive differences may play a key role in determining alien species success in novel environments. Studies that experimentally manipulate competitors while quantifying demography provide mechanistic insight into species’ responses to competition. To date, nearly all field manipulations of competition that measure plant demography and population dynamics have focused on native plant species. The data we provide here aim to address this gap in our knowledge for alien plant species. We present raw data and population‐projection models for 14 alien plant species in eastern Missouri, USA . We sampled under ambient conditions and with all individuals of nonfocal species removed from the community, allowing us to project population dynamics in the presence and absence of competition. We have also included the data quantifying how much biomass we removed at the plot level during each removal procedure and data from our germination experiment. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Major shifts in gut microbiota during development and its relationship to growth in ostriches - Elin Videvall; Se Jin Song; Hanna M. Bensch; Maria Strandh; Anel Engelbrecht; Naomi Serfontein; Olof Hellgren; Adriaan Olivier; Schalk Cloete; Rob Knight; Charlie K. Cornwallis (Molecular Ecology, 2019)
The development of gut microbiota during ontogeny is emerging as an important process influencing physiology, immunity and fitness in vertebrates. However, knowledge of how bacteria colonize the juvenile gut, how this is influenced by changes in the diversity of gut bacteria and to what extent this influences host fitness, particularly in nonmodel organisms, is lacking. Here we used 16S rRNA gene sequencing to describe the successional development of the faecal microbiome in ostriches ( Struthio camelus , n = 66, repeatedly sampled) over the first 3 months of life and its relationship to growth. We found a gradual increase in microbial diversity with age that involved multiple colonization and extinction events and a major taxonomic shift in bacteria that coincided with the cessation of yolk absorption. Comparisons with the microbiota of adults ( n = 5) revealed that the chicks became more similar in their microbial diversity and composition to adults as they aged. There was a five‐fold difference in juvenile growth during development, and growth during the first week of age was strongly positively correlated with the abundance of the genus Bacteroides and negatively correlated with Akkermansia. After the first week, the abundances of six phylogenetically diverse families (Peptococcaceae, S24‐7, Verrucomicrobiae, Anaeroplasmataceae, Streptococcaceae, Methanobacteriaceae) were associated with subsequent reductions in chick growth in an age‐specific and transient manner. These results have broad implications for our understanding of the development of gut microbiota and its associations with animal growth.

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Seedling drought tolerance and functional traits vary in response to the timing of water availability in a keystone Hawaiian tree species - Andrea C. Westerband; Aurora K. Kagawa-Viviani; Kari K. Bogner; David W. Beilman; Tiffany M. Knight; Kasey E. Barton (Plant Ecology, 2019)

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Intracanopy adjustment of leaf-level thermal tolerance is associated with microclimatic variation across the canopy of a desert tree (Acacia papyrocarpa) - Ellen M. Curtis; Charles A. Knight; Andrea Leigh (Oecologia, 2019)

Embracing scale‐dependence to achieve a deeper understanding of biodiversity and its change across communities - Jonathan M. Chase; Brian J. McGill; Daniel J. McGlinn; Felix May; Shane A. Blowes; Xiao Xiao; Tiffany M. Knight; Oliver Purschke; Nicholas J. Gotelli (Ecology Letters, 2018)
Because biodiversity is multidimensional and scale‐dependent, it is challenging to estimate its change. However, it is unclear (1) how much scale‐dependence matters for empirical studies, and (2) if it does matter, how exactly we should quantify biodiversity change. To address the first question, we analysed studies with comparisons among multiple assemblages, and found that rarefaction curves frequently crossed, implying reversals in the ranking of species richness across spatial scales. Moreover, the most frequently measured aspect of diversity – species richness – was poorly correlated with other measures of diversity. Second, we collated studies that included spatial scale in their estimates of biodiversity change in response to ecological drivers and found frequent and strong scale‐dependence, including nearly 10% of studies which showed that biodiversity changes switched directions across scales. Having established the complexity of empirical biodiversity comparisons, we describe a synthesis of methods based on rarefaction curves that allow more explicit analyses of spatial and sampling effects on biodiversity comparisons. We use a case study of nutrient additions in experimental ponds to illustrate how this multi‐dimensional and multi‐scale perspective informs the responses of biodiversity to ecological drivers.

OXI1 kinase plays a key role in resistance of Arabidopsis towards aphids (Myzus persicae) - Tahsin Shoala; Martin G. Edwards; Marc R. Knight; Angharad M. R. Gatehouse (Transgenic Research, 2018)

Reflections on, and visions for, the changing field of pollination ecology - T. M. Knight; T.‐L. Ashman; J. M. Bennett; J. H. Burns; S. Passonneau; J. A. Steets (Ecology Letters, 2018)
Since the launch of Ecology Letters in 1998, the field of Pollination Ecology has changed considerably in its focus. In this review, we discuss the major discoveries across the past two decades. We quantitatively synthesise the frequency by which different concepts and topics appeared in the peer‐reviewed literature, as well as the connections between these topics. We then look forward to identify pressing research frontiers and opportunities for additional integration in the future. We find that there has been a shift towards viewing plant–pollinator interactions as networks and towards understanding how global drivers influence the plants, pollinators and the ecosystem service of pollination. Future frontiers include moving towards a macroecological view of plant–pollinator interactions, understanding how ecological intensification and urbanisation will influence pollination, considering other interactions, such as plant–microbe–pollinator networks, and understanding the causes and consequences of extinctions. Pollination Ecology is poised to advance our basic understanding of the ecological and evolutionary factors that shape plant–animal interactions and to create applied knowledge that informs conservation decision making.

Mapping of new quantitative trait loci for sudden death syndrome and soybean cyst nematode resistance in two soybean populations - Sivakumar Swaminathan; Nilwala S. Abeysekara; Joshua M. Knight; Min Liu; Jia Dong; Matthew E. Hudson; Madan K. Bhattacharyya; Silvia R. Cianzio (Theoretical and Applied Genetics, 2018)

Exotic plant species receive adequate pollinator service despite variable integration into plant–pollinator networks - Amibeth H. Thompson; Tiffany M. Knight (Oecologia, 2018)

Sensory Qualities of Oysters Unaltered by a Short Exposure to Combined Elevated pCO2 and Temperature - Anaëlle J. Lemasson; Victor Kuri; Jason M. Hall-Spencer; Stephen Fletcher; Roy Moate; Antony M. Knights (Frontiers in Marine Science, 2017)

Prioritisation of native legume species for further evaluation as potential forage crops in water-limited agricultural systems in South Africa - Francuois L. Müller; Lincoln M. Raitt; Samson B. M. Chimphango; M. Igshaan Samuels; Clement F. Cupido; J. Stephen Boatwright; Richard Knight; Marike Trytsman (Environmental Monitoring and Assessment, 2017)

The effect of emerald ash borer-caused tree mortality on the invasive shrub Amur honeysuckle and their combined effects on tree and shrub seedlings - Brian M. Hoven; David L. Gorchov; Kathleen S. Knight; Valerie E. Peters (Biological Invasions, 2017)

Supporting sustainability initiatives through biometeorology education and training - Michael J. Allen; Jennifer Vanos; David M. Hondula; Daniel J. Vecellio; David Knight; Hamed Mehdipoor; Rebekah Lucas; Chris Fuhrmann; Hanna Lokys; Angela Lees; Sheila Tavares Nascimento; Andrew C. W. Leung; et al. (International Journal of Biometeorology, 2017)

Application of remote sensing to identify adult plant resistance loci to stripe rust in two bread wheat mapping populations - Z. A. Pretorius; C. X. Lan; R. Prins; V. Knight; N. W. McLaren; R. P. Singh; C. M. Bender; F. J. Kloppers (Precision Agriculture, 2017)

Habitat size modulates the influence of heterogeneity on species richness patterns in a model zooplankton community - Matthew S. Schuler; Jonathan M. Chase; Tiffany M. Knight (Ecology, 2017)
Habitat heterogeneity is a primary mechanism influencing species richness. Despite the general expectation that increased heterogeneity should increase species richness, there is considerable variation in the observed relationship, including many studies that show negative effects of heterogeneity on species richness. One mechanism that can create such disparate results is the predicted trade‐off between habitat area and heterogeneity, sometimes called the area‐heterogeneity‐trade‐off ( AHTO ) hypothesis. The AHTO hypothesis predicts positive effects of heterogeneity on species richness in large habitats, but negative effects in small habitats. We examined the interplay between habitat size and habitat heterogeneity in experimental mesocosms that mimic freshwater ponds, and measured responses in a species‐rich zooplankton community. We used the AHTO hypothesis and related mechanisms to make predictions about how heterogeneity would affect species richness and diversity in large compared to small habitats. We found that heterogeneity had a positive influence on species richness in large, but not small habitats, and that this likely resulted because habitat specialists were able to persist only when habitat size was sufficiently large, consistent with the predictions of the AHTO hypothesis. Our results emphasize the importance of considering context (e.g., habitat size in this case) when investigating the relative importance of ecological drivers of diversity, like heterogeneity.

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Irrigating grazed pasture decreases soil carbon and nitrogen stocks - Paul L. Mudge; Francis M. Kelliher; Trevor L. Knight; Denis O'Connell; Scott Fraser; Louis A. Schipper (Global Change Biology, 2017)
The sustainability of using irrigation to produce food depends not only on the availability of sufficient water, but also on the soil's ‘response’ to irrigation. Stocks of carbon (C) and nitrogen (N) are key components of soil organic matter ( SOM ), which is important for sustainable agricultural production. While there is some information about the effects of irrigation on soil C stocks in cropping systems, there is a paucity of such studies in pastoral food production systems. For this study, we sampled soils from 34 paired, irrigated and unirrigated pasture sites across New Zealand ( NZ ) and analysed these for total C and N. On average, irrigated pastures had significantly ( P 0.05) less soil carbon (C) and nitrogen (N) than adjacent unirrigated pastures, with differences of 6.99 t C ha −1 and 0.58 t N ha −1 in the uppermost 0.3 m. Differences in C and N tended to occur throughout the soil profile, so the cumulative differences increased with depth, and the proportion of the soil C lost from deeper horizons was large. There were no relationships between differences in soil C and N stocks and the length of time under irrigation. This study suggests SOM will decrease when pastures under a temperate climate are irrigated. On this basis, increasing the area of temperate pasture land under irrigation would result in more CO 2 in the atmosphere and may directly and indirectly increase N leaching to groundwater. Given the large and increasing area of land being irrigated both in NZ and on a global scale, there is an urgent need to determine whether the results found in this study are also applicable in other regions and under different land management systems (e.g. arable).

Competition overwhelms the positive plant–soil feedback generated by an invasive plant - Kerri M. Crawford; Tiffany M. Knight (Oecologia, 2017)

Evaluation of laboratory perspectives on hereditary cancer panels - Jessica Stoll; Scott M. Weissman; Nicole Hook; Christina Selkirk; Amy Knight Johnson; Anna Newlin; Kristen J. Vogel Postula (Familial Cancer, 2016)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Fire indirectly benefits fitness in two invasive species - Shannon G. Guthrie; Raelene M. Crandall; Tiffany M. Knight (Biological Invasions, 2016)

Breast cancer survival among young women: a review of the role of modifiable lifestyle factors - Darren R. Brenner; Nigel T. Brockton; Joanne Kotsopoulos; Michelle Cotterchio; Beatrice A. Boucher; Kerry S. Courneya; Julia A. Knight; Ivo A. Olivotto; May Lynn Quan; Christine M. Friedenreich (Cancer Causes & Control, 2016)

Phylogenetic and ecological factors impact the gut microbiota of two Neotropical primate species - Katherine R. Amato; Rodolfo Martinez-Mota; Nicoletta Righini; Melissa Raguet-Schofield; Fabiana Paola Corcione; Elisabetta Marini; Greg Humphrey; Grant Gogul; James Gaffney; Elijah Lovelace; LaShanda Williams; Albert Luong; et al. (Oecologia, 2016)

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Potential Species Replacements for Black Ash (Fraxinus nigra) at the Confluence of Two Threats: Emerald Ash Borer and a Changing Climate - Louis Iverson; Kathleen S. Knight; Anantha Prasad; Daniel A. Herms; Stephen Matthews; Matthew Peters; Annemarie Smith; Diane M. Hartzler; Robert Long; John Almendinger (Ecosystems, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Thermal Inactivation of Feline Calicivirus in Pet Food Processing - J. Haines; M. Patel; A. I. Knight; D. Corley; G. Gibson; J. Schaaf; J. Moulin; S. Zuber (Food and Environmental Virology, 2015)

Intraspecific variation in Fraxinus pennsylvanica responses to emerald ash borer (Agrilus planipennis) - J. L. Koch; D. W. Carey; M. E. Mason; T. M. Poland; K. S. Knight (New Forests, 2015)

Approaching tipping points: a focussed review of indicators and relevance to managing intertidal ecosystems - L. Eslami-Andergoli; P. E. R. Dale; J. M. Knight; H. McCallum (Wetlands Ecology and Management, 2015)

Positive frequency dependence undermines the success of restoration using historical disturbance regimes - Raelene Crandall; Tiffany M. Knight (Ecology Letters, 2015)
Anthropogenic alterations of historical disturbance regimes (e.g. suppressing floods and wildfires) is a primary mechanism by which exotic species can come to dominate native communities. Unfortunately, reinstating historical disturbance regimes to restore native communities has achieved mixed success. The presence of positive frequency dependence ( PFD ) is commonly invoked to explain why exotic plant invasions are so difficult to eradicate. However, models examining PFD have not considered the effect of reintroducing disturbances. Using a spatially explicit individual‐based model, we consider how magnitude and direction of frequency dependence of native and exotic species affects the success of reintroducing disturbances that favour fitness of natives over exotics. Our model illustrates why restoration is difficult; there is a narrow range of parameters that allows for native species to eliminate or coexist with exotics once they have established. Dominance by exotic invaders occurs with moderate initial frequencies of exotic individuals, aggregation of these individuals, or an exotic propagule production advantage. Reintroducing disturbances allows native dominance only when PFD of the exotic is weaker than that of the native species, disturbance intervals are short, and/or exotics are not initially frequent. Our framework provides guidelines for conditions in which the reintroduction of disturbances will effectively restore invaded habitats.

Factors to be Considered in Developing Occupational Regulations for Quad Bikes in Australia - Richard C. Franklin; Kristin E. McBain-Rigg; Sabina M. Knight (Journal of Agromedicine, 2015)

A Semi-Automated, Multi-Source Data Fusion Update of a Wetland Inventory for East-Central Minnesota, USA - Steven M. Kloiber; Robb D. Macleod; Aaron J. Smith; Joseph F. Knight; Brian J. Huberty (Wetlands, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Mangrove rehabilitation: a review focusing on ecological and institutional issues - P. E. R. Dale; J. M. Knight; P. G. Dwyer (Wetlands Ecology and Management, 2014)

Erratum to: A comparative analysis of photosynthetic recovery from thermal stress: a desert plant case study - Ellen M. Curtis; Charles A. Knight; Katherina Petrou; Andrea Leigh (Oecologia, 2014)

A Multidisciplinary Conceptualization of Conservation Opportunity - KATIE MOON; VANESSA M. ADAMS; STEPHANIE R. JANUCHOWSKI‐HARTLEY; MAKSYM POLYAKOV; MORENA MILLS; DUAN BIGGS; ANDREW T. KNIGHT; EDWARD T. GAME; CHRISTOPHER M. RAYMOND (Conservation Biology, 2014)
An opportunity represents an advantageous combination of circumstances that allows goals to be achieved. We reviewed the nature of opportunity and how it manifests in different subsystems (e.g., biophysical, social, political, economic) as conceptualized in other bodies of literature, including behavior, adoption, entrepreneur, public policy, and resilience literature. We then developed a multidisciplinary conceptualization of conservation opportunity. We identified 3 types of conservation opportunity: potential , actors remove barriers to problem solving by identifying the capabilities within the system that can be manipulated to create support for conservation action; traction , actors identify windows of opportunity that arise from exogenous shocks, events, or changes that remove barriers to solving problems; and existing , everything is in place for conservation action (i.e., no barriers exist) and an actor takes advantage of the existing circumstances to solve problems. Different leverage points characterize each type of opportunity. Thus, unique stages of opportunity identification or creation and exploitation exist: characterizing the system and defining problems; identifying potential solutions; assessing the feasibility of solutions; identifying or creating opportunities; and taking advantage of opportunities. These stages can be undertaken independently or as part of a situational analysis and typically comprise the first stage, but they can also be conducted iteratively throughout a conservation planning process. Four types of entrepreneur can be identified (business, policy, social, and conservation), each possessing attributes that enable them to identify or create opportunities and take advantage of them. We examined how different types of conservation opportunity manifest in a social–ecological system (the Great Barrier Reef) and how they can be taken advantage of. Our multidisciplinary conceptualization of conservation opportunity strengthens and legitimizes the concept.

Post-emergent herbicidal activity of cineole derivatives - Allan F. M. Barton; Brenton R. Clarke; Bernard Dell; Allan R. Knight (Journal of Pest Science, 2014)

A comparative analysis of photosynthetic recovery from thermal stress: a desert plant case study - Ellen M. Curtis; Charles A. Knight; Katherina Petrou; Andrea Leigh (Oecologia, 2014)

A high-pressure neutron diffraction study of the ferroelastic phase transition in RbCaF3 - Kevin S. Knight; William G. Marshall; Philip M. Hawkins (Physics and Chemistry of Minerals, 2014)

Impact of familial risk and mammography screening on prognostic indicators of breast disease among women from the Ontario site of the Breast Cancer Family Registry - Meghan J. Walker; Lucia Mirea; Kristine Cooper; Mitra Nabavi; Gord Glendon; Irene L. Andrulis; Julia A. Knight; Frances P. O’Malley; Anna M. Chiarelli (Familial Cancer, 2014)

Differentiating between the supply of N to wheat from above and belowground residues of preceding crops of pea and canola - Melissa M. Arcand; J. Diane Knight; Richard E. Farrell (Biology and Fertility of Soils, 2014)

Nitrogen supply from belowground residues of lentil and wheat to a subsequent wheat crop - Melissa M. Arcand; Reynald Lemke; Richard E. Farrell; J. Diane Knight (Biology and Fertility of Soils, 2014)

The amphibian skin‐associated microbiome across species, space and life history stages - Jordan G. Kueneman; Laura Wegener Parfrey; Douglas C. Woodhams; Holly M. Archer; Rob Knight; Valerie J. McKenzie (Molecular Ecology, 2014)
Skin‐associated bacteria of amphibians are increasingly recognized for their role in defence against pathogens, yet we have little understanding of their basic ecology. Here, we use high‐throughput 16 S r RNA gene sequencing to examine the host and environmental influences on the skin microbiota of the cohabiting amphibian species A naxyrus boreas, P seudacris regilla, T aricha torosa and L ithobates catesbeianus from the C entral V alley in C alifornia. We also studied populations of R ana cascadae over a large geographic range in the K lamath M ountain range of N orthern C alifornia, and across developmental stages within a single site. Dominant bacterial phylotypes on amphibian skin included taxa from B acteroidetes, G ammaproteobacteria, A lphaproteobacteria, F irmicutes, S phingobacteria and A ctinobacteria. Amphibian species identity was the strongest predictor of microbial community composition. Secondarily, within a given amphibian species, wetland site explained significant variation. Amphibian‐associated microbiota differed systematically from microbial assemblages in their environments. Rana cascadae tadpoles have skin bacterial communities distinct from postmetamorphic conspecifics, indicating a strong developmental shift in the skin microbes following metamorphosis. Establishing patterns observed in the skin microbiota of wild amphibians and environmental factors that underlie them is necessary to understand skin symbiont community assembly, and ultimately, the role skin microbiota play in the extended host phenotype including disease resistance.

Symptom Management Strategies for Men with Early-Stage Prostate Cancer: Results from the Prostate Cancer Patient Education Program (PC PEP ) - Alok Vij; Marc A. Kowalkowski; Tae Hart; Heather Honoré Goltz; David J. Hoffman; Sara J. Knight; Peter R. Caroll; David M. Latini (Journal of Cancer Education, 2013)

The genus Pseudo‐nitzschia (Bacillariophyceae) in New Zealand: analysis of the last decade's monitoring data - L Rhodes; W Jiang; B Knight; J Adamson; K Smith; V Langi; M Edgar (New Zealand Journal of Marine and Freshwater Research, 2013)
The diatom genus Pseudo‐nitzschia blooms throughout New Zealand's coastal waters. More than a decade of monitoring data were analysed in this study and seasonality was a significant factor in the appearance of Pseudo‐nitzschia blooms. Austral spring and summer were the main bloom periods, although there were regional differences. Between January 2000 and August 2011, 8.4% of 29,000 seawater samples analysed for Pseudo‐nitzschia exceeded the voluntary trigger level for biotoxin testing (10×10 4 cells l −1 ), and these were analysed by fluorescent in situ hybridisation (FISH) assays. Pseudo‐nitzschia fraudulenta and P. pseudodelicatissima (low domoic acid [DA] producers) were the dominant bloom formers throughout New Zealand (each contributing 25%) followed by the highly toxic P. australis (10%). Shellfish flesh testing for DA was triggered on 8477 occasions between 2000 and 2011, but no samples exceeded the regulatory limit (20 mg/kg); the maximum concentration was 13 mg/kg (Marlborough Sounds, mid‐winter 2010).

The Creation and Maintenance of Wetland Ecosystems from Irrigation Canal and Reservoir Seepage in a Semi-Arid Landscape - Jeremy P. Sueltenfuss; David J. Cooper; Richard L. Knight; Reagan M. Waskom (Wetlands, 2013)

Estimating belowground nitrogen inputs of pea and canola and their contribution to soil inorganic N pools using 15N labeling - Melissa M. Arcand; J. Diane Knight; Richard E. Farrell (Plant and Soil, 2013)

Ability of Matrix Models to Explain the Past and Predict the Future of Plant Populations - ELIZABETH E. CRONE; MARTHA M. ELLIS; WILLIAM F. MORRIS; AMANDA STANLEY; TIMOTHY BELL; PAULETTE BIERZYCHUDEK; JOHAN EHRLÉN; THOMAS N. KAYE; TIFFANY M. KNIGHT; PETER LESICA; GERARD OOSTERMEIJER; PEDRO F. QUINTANA‐ASCENCIO; et al. (Conservation Biology, 2013)
Uncertainty associated with ecological forecasts has long been recognized, but forecast accuracy is rarely quantified. We evaluated how well data on 82 populations of 20 species of plants spanning 3 continents explained and predicted plant population dynamics. We parameterized stage‐based matrix models with demographic data from individually marked plants and determined how well these models forecast population sizes observed at least 5 years into the future. Simple demographic models forecasted population dynamics poorly; only 40% of observed population sizes fell within our forecasts’ 95% confidence limits. However, these models explained population dynamics during the years in which data were collected; observed changes in population size during the data‐collection period were strongly positively correlated with population growth rate. Thus, these models are at least a sound way to quantify population status. Poor forecasts were not associated with the number of individual plants or years of data. We tested whether vital rates were density dependent and found both positive and negative density dependence. However, density dependence was not associated with forecast error. Forecast error was significantly associated with environmental differences between the data collection and forecast periods. To forecast population fates, more detailed models, such as those that project how environments are likely to change and how these changes will affect population dynamics, may be needed. Such detailed models are not always feasible. Thus, it may be wiser to make risk‐averse decisions than to expect precise forecasts from models. Habilidad de los Modelos Matriciales para Explicar el Pasado y Predecir el Futuro de las Poblaciones de Plantas

Soil health as a predictor of lettuce productivity and quality: A case study of urban vacant lots - A. Knight; Z. Cheng; S. S. Grewal; K. R. Islam; M. D. Kleinhenz; P. S. Grewal (Urban Ecosystems, 2013)

Spread of Fusarium pseudograminearum in wheat seedling tissues from a single inoculation point - N. L. Knight; M. W. Sutherland (Australasian Plant Pathology, 2013)

Distribution of platinum-group elements in magmatic and altered ores in the Jinchuan intrusion, China: an example of selenium remobilization by postmagmatic fluids - Hazel M. Prichard; Robert D. Knight; Peter C. Fisher; Iain McDonald; Mei-Fu Zhou; Christina Y. Wang (Mineralium Deposita, 2013)

Biogeographical patterns of variation in Western European populations of the great green bush-cricket (Tettigonia viridissima; Orthoptera Tettigoniidae) - E. M. Cooper; P. H. Lunt; J. S. Ellis; M. E. Knight (Journal of Insect Conservation, 2013)

Genetic and morphometric differences demonstrate fine‐scale population substructure of the yellow perch Perca flavescens : need for redefined management units - P. M. Kocovsky; T. J. Sullivan; C. T. Knight; C. A. Stepien (Journal of Fish Biology, 2013)
Whole‐body morphometrics and 15 nuclear DNA microsatellite loci were analysed for 158 Perca flavescens collected during the spawning season from four spawning locations in central Lake Erie, two along the northern shore and two along the southern shore, to evaluate fine‐scale variation (spanning 17–94 km). Results showed significant morphological and genetic differences among P. flavescens from the four locations. The magnitudes of differences were unrelated to geographic distance, demonstrating spatially heterogeneous levels of genetic divergence. These results linked morphometric and genetic variation, showing a discontinuity of scale between currently defined management units and population structure of P. flavescens in Lake Erie, and support that P. flavescens might exist as one or more metapopulations. Findings demonstrate the value of using complementary techniques for evaluating population structure.

Apple Volatiles Synergize the Response of Codling Moth to Pear Ester - Ashraf M. El-Sayed; Lyn Cole; John Revell; Lee-Anne Manning; Andrew Twidle; Alan L. Knight; Vincent G. M. Bus; David M. Suckling (Journal of Chemical Ecology, 2013)

Scale‐dependent effect sizes of ecological drivers on biodiversity: why standardised sampling is not enough - Jonathan M. Chase; Tiffany M. Knight (Ecology Letters, 2013)
There is little consensus about how natural (e.g. productivity, disturbance) and anthropogenic (e.g. invasive species, habitat destruction) ecological drivers influence biodiversity. Here, we show that when sampling is standardised by area (species density) or individuals (rarefied species richness), the measured effect sizes depend critically on the spatial grain and extent of sampling, as well as the size of the species pool. This compromises comparisons of effects sizes within studies using standard statistics, as well as among studies using meta‐analysis. To derive an unambiguous effect size, we advocate that comparisons need to be made on a scale‐independent metric, such as Hurlbert's Probability of Interspecific Encounter. Analyses of this metric can be used to disentangle the relative influence of changes in the absolute and relative abundances of individuals, as well as their intraspecific aggregations, in driving differences in biodiversity among communities. This and related approaches are necessary to achieve generality in understanding how biodiversity responds to ecological drivers and will necessitate a change in the way many ecologists collect and analyse their data.

Greater sexual reproduction contributes to differences in demography of invasive plants and their noninvasive relatives - Jean H. Burns; Eleanor A. Pardini; Michele R. Schutzenhofer; Y. Anny Chung; Katie J. Seidler; Tiffany M. Knight (Ecology, 2013)
An understanding of the demographic processes contributing to invasions would improve our mechanistic understanding of the invasion process and improve the efficiency of prevention and control efforts. However, field comparisons of the demography of invasive and noninvasive species have not previously been conducted. We compared the in situ demography of 17 introduced plant species in St. Louis, Missouri, USA, to contrast the demographic patterns of invasive species with their less invasive relatives across a broad sample of angiosperms. Using herbarium records to estimate spread rates, we found higher maximum spread rates in the landscape for species classified a priori as invasive than for noninvasive introduced species, suggesting that expert classifications are an accurate reflection of invasion rate. Across 17 species, projected population growth was not significantly greater in invasive than in noninvasive introduced species. Among five taxonomic pairs of close relatives, however, four of the invasive species had higher projected population growth rates compared with their noninvasive relative. A Life Table Response Experiment suggested that the greater projected population growth rate of some invasive species relative to their noninvasive relatives was primarily a result of sexual reproduction. The greater sexual reproduction of invasive species is consistent with invaders having a life history strategy more reliant on fecundity than survival and is consistent with a large role of propagule pressure in invasion. Sexual reproduction is a key demographic correlate of invasiveness, suggesting that local processes influencing sexual reproduction, such as enemy escape, might be of general importance. However, the weak correlation of projected population growth with spread rates in the landscape suggests that regional processes, such as dispersal, may be equally important in determining invasion rate.

The molecular identification and genetic diversity of economically important wireworm species (Coleoptera: Elateridae) in Canada - Carly M. Benefer; W. G. van Herk; J. S. Ellis; R. P. Blackshaw; R. S. Vernon; M. E. Knight (Journal of Pest Science, 2013)

A respiratory alert model for the Shenandoah Valley, Virginia, USA - David M. Hondula; Robert E. Davis; David B. Knight; Luke J. Sitka; Kyle Enfield; Stephen B. Gawtry; Phillip J. Stenger; Michael L. Deaton; Caroline P. Normile; Temple R. Lee (International Journal of Biometeorology, 2013)

Shifts in pollinator composition and behavior cause slow interaction accumulation with area in plant–pollinator networks - Laura A. Burkle; Tiffany M. Knight (Ecology, 2012)
Although ecologists have a solid understanding of the positive species–area relationship, little is known about how and why variation in habitat area influences the richness, structure, and function of species interaction networks. To address this, we investigated plant–pollinator interaction networks of the herbaceous rocky outcrop communities in Ozark glades (Missouri, USA) of different areas. We quantified the degree to which the increase in the number of species interactions with area differed from a null model based on sampling, where numbers of individuals increase with area. Although plant–pollinator interactions were expected to increase more steeply with area than species richness as a result of sampling, the observed rate of increase was considerably lower than expected. Two mechanisms could lead to this pattern: a higher proportion of specialist species in larger glades or generalist pollinators becoming more selective in their diets in larger glades. We found support for the former hypothesis, and those changes in species composition were strong enough to outweigh behavioral changes in the opposite direction; generalist pollinators were more selective in smaller glades. If these results are general, larger habitats may be needed to conserve interactions than would be thought based on species accumulation curves.

Managing mosquitoes without destroying wetlands: an eastern Australian approach - P. E. R. Dale; J. M. Knight (Wetlands Ecology and Management, 2012)

A review of the role of fish as biological control agents of disease vector mosquitoes in mangrove forests: reducing human health risks while reducing environmental risk - Lachlan F. Griffin; Jon M. Knight (Wetlands Ecology and Management, 2012)

Patterns of selection and polymorphism of innate immunity genes in bumblebees (Hymenoptera: Apidae) - J. S. Ellis; L. M. Turner; M. E. Knight (Genetica, 2012)

Population genetic structure and long‐distance dispersal among seabird populations: Implications for colony persistence - A. W. J. BICKNELL; M. E. KNIGHT; D. BILTON; J. B. REID; T. BURKE; S. C. VOTIER (Molecular Ecology, 2012)
Dramatic local population decline brought about by anthropogenic‐driven change is an increasingly common threat to biodiversity. Seabird life history traits make them particularly vulnerable to such change; therefore, understanding population connectivity and dispersal dynamics is vital for successful management. Our study used a 357‐base pair mitochondrial control region locus sequenced for 103 individuals and 18 nuclear microsatellite loci genotyped for 245 individuals to investigate population structure in the Atlantic and Pacific populations of the pelagic seabird, Leach’s storm‐petrel Oceanodroma leucorhoa leucorhoa . This species is under intense predation pressure at one regionally important colony on St Kilda, Scotland, where a disparity between population decline and predation rates hints at immigration from other large colonies. amova , F ST, Φ ST and Bayesian cluster analyses revealed no genetic structure among Atlantic colonies (Global Φ ST = −0.02 P > 0.05, Global F ST = 0.003, P > 0.05, structure K = 1), consistent with either contemporary gene flow or strong historical association within the ocean basin. The Pacific and Atlantic populations are genetically distinct (Global Φ ST = 0.32 P F ST = 0.04, P structure K = 2), but evidence for interocean exchange was found with individual exclusion/assignment and population coalescent analyses. These findings highlight the importance of conserving multiple colonies at a number of different sites and suggest that management of this seabird may be best viewed at an oceanic scale. Moreover, our study provides an illustration of how long‐distance movement may ameliorate the potentially deleterious impacts of localized environmental change, although direct measures of dispersal are still required to better understand this process.

Matrix population models from 20 studies of perennial plant populations - Martha M. Ellis; Jennifer L. Williams; Peter Lesica; Timothy J. Bell; Paulette Bierzychudek; Marlin Bowles; Elizabeth E. Crone; Daniel F. Doak; Johan Ehrlén; Albertine Ellis-Adam; Kathryn McEachern; Rengaian Ganesan; et al. (Ecology, 2012)
Demographic transition matrices are among the most commonly applied population models for both basic and applied ecological research. The relatively simple framework of these models and simple, easily interpretable summary statistics they produce have prompted the wide use of these models across an exceptionally broad range of taxa. Here, we provide annual transition matrices and observed stage structures/population sizes for 20 perennial plant species which have been the focal species for long‐term demographic monitoring. These data were assembled as part of the “Testing Matrix Models” working group through the National Center for Ecological Analysis and Synthesis (NCEAS). The data represent 82 populations with >460 total population‐years of observations. It is our hope that making these data available will help promote and improve our ability to monitor and understand plant population dynamics. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

A Model of Mosquito–Mangrove Basin Ecosystems with Implications for Management - Jon M. Knight (Ecosystems, 2011)

Hybridisation of Australian chickpea cultivars with wild Cicer spp. increases resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) - John P. Thompson; Roslyn A. Reen; Timothy G. Clewett; Jason G. Sheedy; Alison M. Kelly; Beverley J. Gogel; Edward J. Knights (Australasian Plant Pathology, 2011)

Motueka River plume facilitates transport of ruminant faecal contaminants into shellfish growing waters, Tasman Bay, New Zealand - CD Cornelisen; PA Gillespie; M Kirs; RG Young; RW Forrest; PJ Barter; BR Knight; VJ Harwood (New Zealand Journal of Marine and Freshwater Research, 2011)
Hydrographic and water quality surveys of the Motueka River and its river plume were conducted during a moderate flood event (peak flow of 420 m 3 /s) to assess the source and fate of faecal contaminants transported into Tasman Bay. Escherichia coli ( E . coli ) and enterococci concentrations in the river were up to 10000 and 7300 Most Probable Number (MPN)/100 ml during peak flow, respectively. A coastal survey revealed a shallow low‐salinity plume that extended at least 6 km into Tasman Bay and the region's largest aquaculture management areas (AMAs). Mussels within the influence of the river plume, including those collected within an AMA, had E . coli and enterococci concentrations as high as 1300 and 2200 MPN/100 g tissue, respectively. Application of microbial source tracking markers using end‐point PCR assays identified the presence of faecal contamination from ruminant animals (cows, sheep) in water and mussel samples. The detection of ruminant faecal contamination within shellfish located 6 km offshore highlights the close connection between land use and the quality of New Zealand's highly valued coastal resources.

A phylogenetically controlled analysis of the roles of reproductive traits in plant invasions - Jean H. Burns; Tia-Lynn Ashman; Janette A. Steets; Alexandra Harmon-Threatt; Tiffany M. Knight (Oecologia, 2011)

Comparing the reproductive success and pollination biology of an invasive plant to its rare and common native congeners: a case study in the genus Cirsium (Asteraceae) - Kristin I. Powell; Kyra N. Krakos; Tiffany M. Knight (Biological Invasions, 2011)

The potential of pulsed low intensity ultrasound to stimulate chondrocytes matrix synthesis in agarose and monolayer cultures - Natalie M. Vaughan; James Grainger; Dan L. Bader; Martin M. Knight (Medical & Biological Engineering & Computing, 2010)

Climate change and the green energy paradox: the consequences for twaite shad Alosa fallax from the River Severn, U.K. - M. W. Aprahamian; C. D. Aprahamian; A. M. Knights (Journal of Fish Biology, 2010)
A stock–recruitment model with a temperature component was used to estimate the effect of an increase in temperature predicted by climate change projections on population persistence and distribution of twaite shad Alosa fallax . An increase of 1 and 2° C above the current mean summer (June to August) water temperature of 17·8° C was estimated to result in a three and six‐fold increase in the population, respectively. Climate change is also predicted to result in an earlier commencement to their spawning migration into fresh water. The model was expanded to investigate the effect of any additional mortality that might arise from a tidal power barrage across the Severn Estuary. Turbine mortality was separated into two components: (1) juvenile (pre‐maturation) on their out migration during their first year and on their first return to the river to spawn and (2) post‐maturation mortality on adults on the repeat spawning component of the population. Under current conditions, decreasing pre‐maturation and post‐maturation survival by 8% is estimated to result in the stock becoming extinct. It is estimated that an increase in mean summer water temperature of 1° C would mean that survival pre and post‐maturation would need to be reduced by c . 10% before the stock becomes extinct. Therefore, climate change is likely to be beneficial to populations of A. fallax within U.K. rivers, increasing survival and thus, population persistence.

The ecology of the phyllosphere: geographic and phylogenetic variability in the distribution of bacteria on tree leaves - Amanda J. Redford; Robert M. Bowers; Rob Knight; Yan Linhart; Noah Fierer (Environmental Microbiology, 2010)
Summary Large populations of bacteria live on leaf surfaces and these phyllosphere bacteria can have important effects on plant health. However, we currently have a limited understanding of bacterial diversity on tree leaves and the inter‐ and intra‐specific variability in phyllosphere community structure. We used a barcoded pyrosequencing technique to characterize the bacterial communities from leaves of 56 tree species in Boulder, Colorado, USA, quantifying the intra‐ and inter‐individual variability in the bacterial communities from 10 of these species. We also examined the geographic variability in phyllosphere communities on Pinus ponderosa from several locations across the globe. Individual tree species harboured high levels of bacterial diversity and there was considerable variability in community composition between trees. The bacterial communities were organized in patterns predictable from the relatedness of the trees as there was significant correspondence between tree phylogeny and bacterial community phylogeny. Inter‐specific variability in bacterial community composition exceeded intra‐specific variability, a pattern that held even across continents where we observed minimal geographic differentiation in the bacterial communities on P. ponderosa needles.

Identifying Mosquito Habitat Microtopography in an Australian Mangrove Forest Using LiDAR Derived Elevation Data - Lachlan F. Griffin; Jon M. Knight; Pat E. R. Dale (Wetlands, 2010)

The effects of pollen limitation on population dynamics of snow lotus (Saussurea medusa and S. laniceps, Asteraceae): Threatened Tibetan medicinal plants of the eastern Himalayas - Wayne Law; Jan Salick; Tiffany M. Knight (Plant Ecology, 2010)

Mapping Human and Social Dimensions of Conservation Opportunity for the Scheduling of Conservation Action on Private Land - ANDREW T. KNIGHT; RICHARD M. COWLING; MARK DIFFORD; BRUCE M. CAMPBELL (Conservation Biology, 2010)
Spatial prioritization techniques are applied in conservation‐planning initiatives to allocate conservation resources. Although typically they are based on ecological data (e.g., species, habitats, ecological processes), increasingly they also include nonecological data, mostly on the vulnerability of valued features and economic costs of implementation. Nevertheless, the effectiveness of conservation actions implemented through conservation‐planning initiatives is a function of the human and social dimensions of social‐ecological systems, such as stakeholders’ willingness and capacity to participate. We assessed human and social factors hypothesized to define opportunities for implementing effective conservation action by individual land managers (those responsible for making day‐to‐day decisions on land use) and mapped these to schedule implementation of a private land conservation program. We surveyed 48 land managers who owned 301 land parcels in the Makana Municipality of the Eastern Cape province in South Africa. Psychometric statistical and cluster analyses were applied to the interview data so as to map human and social factors of conservation opportunity across a landscape of regional conservation importance. Four groups of landowners were identified, in rank order, for a phased implementation process. Furthermore, using psychometric statistical techniques, we reduced the number of interview questions from 165 to 45, which is a preliminary step toward developing surrogates for human and social factors that can be developed rapidly and complemented with measures of conservation value, vulnerability, and economic cost to more‐effectively schedule conservation actions. This work provides conservation and land management professionals direction on where and how implementation of local‐scale conservation should be undertaken to ensure it is feasible.

Causes and consequences of variation in plant population growth rate: a synthesis of matrix population models in a phylogenetic context - Yvonne M. Buckley; Satu Ramula; Simon P. Blomberg; Jean H. Burns; Elizabeth E. Crone; Johan Ehrlén; Tiffany M. Knight; Jean‐Baptiste Pichancourt; Helen Quested; Glenda M. Wardle (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1182–1197 Abstract Explaining variation in population growth rates is fundamental to predicting population dynamics and population responses to environmental change. In this study, we used matrix population models, which link birth, growth and survival to population growth rate, to examine how and why population growth rates vary within and among 50 terrestrial plant species. Population growth rates were more similar within species than among species; with phylogeny having a minimal influence on among‐species variation. Most population growth rates decreased over the observation period and were negatively autocorrelated between years; that is, higher than average population growth rates tended to be followed by lower than average population growth rates. Population growth rates varied more through time than space; this temporal variation was due mostly to variation in post‐seedling survival and for a subset of species was partly explained by response to environmental factors, such as fire and herbivory. Stochastic population growth rates departed from mean matrix population growth rate for temporally autocorrelated environments. Our findings indicate that demographic data and models of closely related plant species cannot necessarily be used to make recommendations for conservation or control, and that post‐seedling survival and the sequence of environmental conditions are critical for determining plant population growth rate.

Apparent competition with an invasive plant hastens the extinction of an endangered lupine - Emily M. Dangremond; Eleanor A. Pardini; Tiffany M. Knight (Ecology, 2010)
Invasive plants may compete with native plants by increasing the pressure of native consumers, a mechanism known as “apparent competition.” Apparent competition can be as strong as or stronger than direct competition, but the role of apparent competition has rarely been examined in biological invasions. We used four years of demographic data and seed‐removal experiments to determine if introduced grasses caused elevated levels of seed consumption on native plant species in a coastal dune system in California, USA. We show that the endangered, coastal dune plant Lupinus tidestromii experiences high levels of pre‐dispersal seed consumption by the native rodent Peromyscus maniculatus due to its proximity to the invasive grass, Ammophila arenaria . We use stage‐structured, stochastic population models to project that two of three study populations will decline toward extinction under ambient levels of consumption. For one of these declining populations, a relatively small decrease in consumption pressure should allow for persistence. We show that apparent competition with an invasive species significantly decreases the population growth rate and persistence of a native species. We expect that apparent competition is an important mechanism in other ecosystems because invasive plants often change habitat structure and plant–consumer interactions. Possible implications of the apparent‐competition mechanism include selective extinction of species preferred by seed consumers in the presence of an invasive species and biological homogenization of communities toward non‐preferred native plant species.

Calmodulin-binding transcription activator 1 mediates auxin signaling and responds to stresses in Arabidopsis - Yael Galon; Roni Aloni; Dikla Nachmias; Orli Snir; Ester Feldmesser; Sarah Scrase-Field; Joy M. Boyce; Nicolas Bouché; Marc R. Knight; Hillel Fromm (Planta, 2010)

The importance of coastal sand dunes for terrestrial invertebrates in Wales and the UK, with particular reference to aculeate Hymenoptera (bees, wasps & ants) - M. A. Howe; G. T. Knight; C. Clee (Journal of Coastal Conservation, 2010)

Toxicity Evaluation of a Conservation Effects Assessment Program Watershed, Beasley Lake, in the Mississippi Delta, USA - Richard E. Lizotte; Scott S. Knight; Charles M. Cooper (Bulletin of Environmental Contamination and Toxicology, 2010)

Invest in Opportunity, Not Inventory of Hotspots - RICHARD M. COWLING; ANDREW T. KNIGHT; SEAN D. J. PRIVETT; GYAN SHARMA (Conservation Biology, 2010)

A back‐trajectory and air mass climatology for the Northern Shenandoah Valley, USA - David M. Hondula; Luke Sitka; Robert E. Davis; David B. Knight; Stephen D. Gawtry; Michael L. Deaton; Temple R. Lee; Caroline P. Normile; Philip J. Stenger (International Journal of Climatology, 2010)
Synoptic‐scale air quality climatologies can often be categorized into trajectory methods based on air parcel movement or air mass approaches that are primarily dictated by thermal and moisture conditions. Here, we examine the relationship between these two essentially independent methods of synoptic‐scale climate classification: 72‐h Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model back‐trajectories and the Spatial Synoptic Classification (SSC) of air masses for Martinsburg, West Virginia, located at the northern end of the Shenandoah Valley, from 1997 to 2006. Statistically significant differences exist between trajectory groups across the six SSC air mass types within each season and between seasons within each air mass type. Further examination of the trajectory distributions reveals a high degree of overlap between trajectories associated with different air mass types. In some cases, up to 50% of one air mass's trajectories are statistically closer to the trajectories of a different air mass type. Accordingly, air mass alone cannot be used to identify specific source regions of pollutants. This suggests that, while an air mass classification system can be used to identify general flow patterns, the integration of both thermodynamic and air‐flow variables in a synoptic classification should provide information that is not discernible from either method independently. The inclusion of both back‐trajectory and air mass information represents the suite of environmental conditions that may enhance or suppress pollutant concentrations in the Shenandoah Valley better than using either measure independently. Copyright © 2009 Royal Meteorological Society

Vitamin D association with estradiol and progesterone in young women - Julia A. Knight; Jody Wong; Kristina M. Blackmore; Janet M. Raboud; Reinhold Vieth (Cancer Causes & Control, 2010)

Night sampling improves indices used for management of yellow perch in Lake Erie - P. M. KOCOVSKY; M. A. STAPANIAN; C. T. KNIGHT (Fisheries Management and Ecology, 2010)
Catch rate (catch per hour) was examined for age‐0 and age‐1 yellow perch, Perca flavescens (Mitchill), captured in bottom trawls from 1991 to 2005 in western Lake Erie: (1) to examine variation of catch rate among years, seasons, diel periods and their interactions; and (2) to determine whether sampling during particular diel periods improved the management value of CPH data used in models to project abundance of age‐2 yellow perch. Catch rate varied with year, season and the diel period during which sampling was conducted as well as by the interaction between year and season. Indices of abundance of age‐0 and age‐1 yellow perch estimated from night samples typically produced better fitting models and lower estimates of age‐2 abundance than those using morning or afternoon samples, whereas indices using afternoon samples typically produced less precise and higher estimates of abundance. The diel period during which sampling is conducted will not affect observed population trends but may affect estimates of abundance of age‐0 and age‐1 yellow perch, which in turn affect recommended allowable harvest. A field experiment throughout western Lake Erie is recommended to examine potential benefits of night sampling to management of yellow perch.

An investigation of genetic variation among Australian isolates of Bipolaris sorokiniana from different cereal tissues and comparison of their abilities to cause spot blotch on barley - N. L. Knight; G. J. Platz; A. Lehmensiek; M. W. Sutherland (Australasian Plant Pathology, 2010)

The CLIVAR C20C project: which components of the Asian–Australian monsoon circulation variations are forced and reproducible? - Tianjun Zhou; Bo Wu; A. A. Scaife; S. Brönnimann; A. Cherchi; D. Fereday; A. M. Fischer; C. K. Folland; K. E. Jin; J. Kinter; J. R. Knight; F. Kucharski; et al. (Climate Dynamics, 2009)

A Cost Effective Method to Enhance Dredge Mine Reconciliation in Heavy Minerals Mining Industry - G. V. I. Samaradivakara; M. Kizil; P. Knights (Marine Georesources & Geotechnology, 2009)

The CLIVAR C20C project: skill of simulating Indian monsoon rainfall on interannual to decadal timescales. Does GHG forcing play a role? - F. Kucharski; A. A. Scaife; J. H. Yoo; C. K. Folland; J. Kinter; J. Knight; D. Fereday; A. M. Fischer; E. K. Jin; J. Kröger; N.-C. Lau; T. Nakaegawa; et al. (Climate Dynamics, 2009)

The CLIVAR C20C project: selected twentieth century climate events - A. A. Scaife; F. Kucharski; C. K. Folland; J. Kinter; S. Brönnimann; D. Fereday; A. M. Fischer; S. Grainger; E. K. Jin; I. S. Kang; J. R. Knight; S. Kusunoki; et al. (Climate Dynamics, 2009)

An in vivo model of melanoma: treatment with ATP - Nicholas White; Gillian E. Knight; Peter E. M. Butler; Geoffrey Burnstock (Purinergic Signalling, 2009)

Herbivory and population dynamics of invasive and native Lespedeza - Michele R. Schutzenhofer; Thomas J. Valone; Tiffany M. Knight (Oecologia, 2009)

Twenty‐four hours in the life of Zingel asper - L. Cavalli; C.M. Knight; M. Durbec; R. Chappaz; R.E. Gozlan (Journal of Fish Biology, 2009)
For the first time, radio‐tracking observations were made over 24 h cycles during the growing season to quantify the habitat use and home range of Zingel asper , a critically endangered fish species, endemic to the Rhône River with a high risk of extinction (IUCN). New advances in radio telemetry with regard to the size of tags provided an opportunity to collect behavioural and habitat use information while remaining non‐lethal. Zingel asper was characterized by small ranges of habitat use and, contrary to previous assumptions, the species was diurnal as illustrated by a smaller home range during the night than during daytime.

Interactive Effects of Harvest and Deer Herbivory on the Population Dynamics of American Ginseng - SUSAN J. FARRINGTON; ROSE‐MARIE MUZIKA; DAN DREES; TIFFANY M. KNIGHT (Conservation Biology, 2009)
Few demographic models for any species consider the role of multiple, interacting ecological threats. Many forest herbs are heavily browsed by white‐tailed deer ( Odocoileus virginianus ) and a number of these are also harvested for the medicinal, floral, or horticultural trades. Previous studies of the viability of American ginseng ( Panax quinquefolius ) have separately examined the effects of harvesting and deer herbivory. We followed individually marked ginseng plants in 6 populations for 8 years and documented deer browse levels, conducted helicopter surveys to estimate the deer herd size, and documented 2 ginseng harvests. We used this long‐term data set to develop a stochastic demographic model that quantified the separate and interactive role of these threats to ginseng viability. Although harvesting and deer herbivory negatively affected ginseng population growth, their effects were not additive. Deer herbivory negatively affected population growth in the absence but not in the presence of harvesting. Life table response experiments revealed that in the presence of harvesting, deer herbivory had some positive effects on vital rates because browsed plants were less apparent to harvesters. Ginseng populations that were harvested responsibly (i.e., planting seeds from harvested individuals) had higher growth rates than those that were harvested irresponsibly. We concluded that both deer populations and harvesting must be managed to ensure sustainable populations of American ginseng. Our findings underscore the importance of long‐term monitoring to assess threats to viability and the need for a broad ecological understanding of the complexity of ecosystem management.

Mississippi Oxbow Lake Sediment Quality During an Artificial Flood - S. S. Knight; R. E. Lizotte; M. T. Moore; S. Smith; F. D. Shields (Bulletin of Environmental Contamination and Toxicology, 2009)

Biomechanical analysis of structural deformation in living cells - D. L. Bader; M. M. Knight (Medical & Biological Engineering & Computing, 2008)

Clearing the Mud from the Conservation Opportunity Debate: Reply to Pressey and Bottrill - ANDREW T. KNIGHT; RICHARD M. COWLING (Conservation Biology, 2008)

Can seasonal home‐range size in pike Esox lucius predict excursion distance? - C. M. Knight; R. E. Gozlan; M. C. Lucas (Journal of Fish Biology, 2008)
The hypothesis that vagility, or tendency to move, in pike Esox lucius can be predicted from individual home range was tested using telemetry. Independently of fish size, mean annual excursion distance was positively correlated to winter (0·02–0·95 ha) and spring (0·02–0·59 ha) home ranges but not summer and autumn home ranges.

Wetlands and mosquitoes: a review - P. E. R. Dale; J. M. Knight (Wetlands Ecology and Management, 2008)

Knowing But Not Doing: Selecting Priority Conservation Areas and the Research–Implementation Gap - ANDREW T. KNIGHT; RICHARD M. COWLING; MATHIEU ROUGET; ANDREW BALMFORD; AMANDA T. LOMBARD; BRUCE M. CAMPBELL (Conservation Biology, 2008)
Conservation assessment is a rapidly evolving discipline whose stated goal is the design of networks of protected areas that represent and ensure the persistence of nature (i.e., species, habitats, and environmental processes) by separating priority areas from the activities that degrade or destroy them. Nevertheless, despite a burgeoning scientific literature that ever refines these techniques for allocating conservation resources, it is widely believed that conservation assessments are rarely translated into actions that actually conserve nature. We reviewed the conservation assessment literature in peer‐reviewed journals and conducted survey questionnaires of the authors of these studies. Two‐thirds of conservation assessments published in the peer‐reviewed scientific literature do not deliver conservation action, primarily because most researchers never plan for implementation. This research–implementation gap between conservation science and real‐world action is a genuine phenomenon and is a specific example of the “knowing–doing gap” that is widely recognized in management science. Given the woefully inadequate resources allocated for conservation, our findings raise questions over the utility of conservation assessment science, as currently practiced, to provide useful, pragmatic solutions to conservation planning problems. A reevaluation of the conceptual and operational basis of conservation planning research is urgently required. We recommend the following actions for beginning a process for bridging the research–implementation gap in conservation planning: (1) acknowledge the research–implementation gap is real, (2) source research questions from practitioners, (3) situate research within a broader conservation planning model, (4) expand the social dimension of conservation assessments, (5) support conservation plans with transdisciplinary social learning institutions, (6) reward academics for societal engagement and implementation, and (7) train students in skills for “doing” conservation.

Integrated bioinformatic and phenotypic analysis of RpoN‐dependent traits in the plant growth‐promoting bacterium Pseudomonas fluorescens SBW25 - Jacob Jones; David J. Studholme; Christopher G. Knight; Gail M. Preston (Environmental Microbiology, 2007)
Summary The alternative sigma factor RpoN is a key regulator in the acclimation of Pseudomonas to complex natural environments. In this study we show that RpoN is required for efficient colonization of sugar beet seedlings by the plant growth‐promoting bacterium Pseudomonas fluorescens SBW25, and use phenotypic and bioinformatic approaches to profile the RpoN‐dependent traits and genes of P. fluorescens SBW25. RpoN is required for flagellar biosynthesis and for assimilation of a wide variety of nutrient sources including inorganic nitrogen, amino acids, sugar alcohols and dicarboxylic acids. Chemosensitivity assays indicate that RpoN‐regulated genes contribute to acid tolerance and resistance to some antibiotics, including tetracyclines and aminoglycosides. Gain of function changes associated with loss of RpoN included increased tolerance to hydroxyurea and Guanazole. Bioinformatic predictions of RpoN‐regulated genes show a close correspondence with phenotypic analyses of RpoN‐regulated traits and suggest novel functions for RpoN in P. fluorescens , including regulation of poly(A) polymerase. The reduced plant colonization ability observed for an rpoN mutant of P. fluorescens is therefore likely to be due to defects in multiple traits including nutrient assimilation, protein secretion and stress tolerance.

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

Embracing Opportunism in the Selection of Priority Conservation Areas - ANDREW T. KNIGHT; RICHARD M. COWLING (Conservation Biology, 2007)

Can Warmwater Streams Be Rehabilitated Using Watershed-Scale Standard Erosion Control Measures Alone? - F. Douglas Shields; Scott S. Knight; Charles M. Cooper (Environmental Management, 2007)

Techniques for evaluating the spatial behaviour of river fish - Kathy H. Hodder; Jerome E. G. Masters; William R. C. Beaumont; Rodolphe E. Gozlan; Adrian C. Pinder; Carolyn M. Knight; Robert E. Kenward (Hydrobiologia, 2007)

Ionic Contra-Viral Therapy (ICVT); a new approach to the treatment of DNA virus infections - C. Hartley; M. Hartley; I. Pardoe; A. Knight (Archives of Virology, 2006)

Effects of eutrophication and snails on Eurasian watermilfoil (Myriophyllum spicatum) invasion - Jonathan M. Chase; Tiffany M. Knight (Biological Invasions, 2006)

Extremely low effective population sizes, genetic structuring and reduced genetic diversity in a threatened bumblebee species, Bombus sylvarum (Hymenoptera: Apidae) - J. S. ELLIS; M. E. KNIGHT; B. DARVILL; D. GOULSON (Molecular Ecology, 2006)
Habitat fragmentation may severely affect survival of social insect populations as the number of nests per population, not the number of individuals, represents population size, hence they may be particularly prone to loss of genetic diversity. Erosion of genetic diversity may be particularly significant among social Hymenoptera such as bumblebees ( Bombus spp.), as this group may be susceptible to diploid male production, a suggested direct cost of inbreeding. Here, for the first time, we assess genetic diversity and population structuring of a threatened bumblebee species ( Bombus sylvarum ) which exists in highly fragmented habitat (rather than oceanic) islands. Effective population sizes, estimated from identified sisterhoods, were very low (range 21–72) suggesting that isolated populations will be vulnerable to loss of genetic variation through drift. Evidence of significant genetic structuring between populations (θ = 0.084) was found, but evidence of a bottleneck was detected in only one population. Comparison across highly fragmented UK populations and a continental population (where this species is more widespread) revealed significant differences in allelic richness attributable to a high degree of genetic diversity in the continental population. While not directly related to population size, this is perhaps explained by the high degree of isolation between UK populations relative to continental populations. We suggest that populations now existing on isolated habitat islands were probably linked by stepping‐stone populations prior to recent habitat loss.

Predation on mutualists can reduce the strength of trophic cascades - Tiffany M. Knight; Jonathan M. Chase; Helmut Hillebrand; Robert D. Holt (Ecology Letters, 2006)
Ecologists have put forth several mechanisms to predict the strength of predator effects on producers (a trophic cascade). We suggest a novel mechanism – in systems in which mutualists of plants are present and important, predators can have indirect negative effects on producers through their consumption of mutualists. The strength of predator effects on producers will depend on their relative consumption of mutualists and antagonists, and on the relative importance of each to producer population dynamics. In a meta‐analysis of experiments that examine the effects of predator reduction on the pollination and reproductive success of plants, we found that the indirect negative effects of predators on plants are quite strong. Most predator removal experiments measure the strength of predator effects on producers through the antagonist pathway; we suggest that a more complete understanding of the role of predators will be achieved by simultaneously considering the effects of predators on plant mutualists.

Managing Salt Marshes for Mosquito Control: Impacts of Runnelling, Open Marsh Water Management and Grid-ditching in Sub-tropical Australia - Pat E. R. Dale; Jon M. Knight (Wetlands Ecology and Management, 2006)

Designing Systematic Conservation Assessments that Promote Effective Implementation: Best Practice from South Africa - ANDREW T. KNIGHT; AMANDA DRIVER; RICHARD M. COWLING; KRISTAL MAZE; PHILIP G. DESMET; AMANDA T. LOMBARD; MATHIEU ROUGET; MARK A. BOTHA; ANDRE F. BOSHOFF; J. GUY CASTLEY; PETER S. GOODMAN; KATHY MACKINNON; et al. (Conservation Biology, 2006)
Systematic conservation assessment and conservation planning are two distinct fields of conservation science often confused as one and the same. Systematic conservation assessment is the technical, often computer‐based, identification of priority areas for conservation. Conservation planning is composed of a systematic conservation assessment coupled with processes for development of an implementation strategy and stakeholder collaboration. The peer‐reviewed conservation biology literature abounds with studies analyzing the performance of assessments (e.g., area‐selection techniques). This information alone, however, can never deliver effective conservation action; it informs conservation planning. Examples of how to translate systematic assessment outputs into knowledge and then use them for “doing” conservation are rare. South Africa has received generous international and domestic funding for regional conservation planning since the mid‐1990s. We reviewed eight South African conservation planning processes and identified key ingredients of best practice for undertaking systematic conservation assessments in a way that facilitates implementing conservation action. These key ingredients include the design of conservation planning processes, skills for conservation assessment teams, collaboration with stakeholders, and interpretation and mainstreaming of products (e.g., maps) for stakeholders. Social learning institutions are critical to the successful operationalization of assessments within broader conservation planning processes and should include not only conservation planners but also diverse interest groups, including rural landowners, politicians, and government employees.

A Review of Fine Root Dynamics in Populus Plantations - R. M. A. Block; K. C. J. Van Rees; J. D. Knight (Agroforestry Systems, 2006)

An Operational Model for Implementing Conservation Action - ANDREW T. KNIGHT; RICHARD M. COWLING; BRUCE M. CAMPBELL (Conservation Biology, 2006)
The preoccupation of many conservation planners with the refinement of systematic assessment techniques has manifested an “implementation crisis” in conservation planning. This preoccupation has provided systematic assessments with well‐tested tools (e.g., area selection algorithms) and principles (e.g., representation, complementarity), but our understanding of these techniques currently far exceeds our ability to apply them effectively to pragmatic conservation problems. The science is informative about where one needs to do conservation, but silent on how to achieve it. Operational models, defined as simplified conceptualizations of processes for implementing conservation action at priority conservation areas, are essential for guiding conservation planning initiatives because they assist understanding of how these processes function. Operational models developed to date have largely been linear, simplistic, and focused on the systematic assessment of biological entities. Experience in the real world indicates that operational models for conducting conservation planning initiatives should explicitly complement a systematic conservation assessment with activities that empower individuals and institutions (enabling) and explicitly aim to secure conservation action (implementation). Specifically, implementing effective conservation action requires that systematic assessments be integrated functionally with a process for developing an implementation strategy and processes for stakeholder collaboration while maintaining a broad focus on the implementation of conservation action. A suite of hallmarks define effective operational models (e.g., stakeholder collaboration, links with land‐use planning, social learning, and action research). Greater development and testing of the practical application of operational models should lead to higher levels of effective implementation and alleviate the implementation crisis. Social learning institutions are essential for ensuring ongoing improvement in the development and application of operational models that deliver effective conservation action.

Designing Large‐Scale Conservation Corridors for Pattern and Process - MATHIEU ROUGET; RICHARD M. COWLING; AMANDA T. LOMBARD; ANDREW T. KNIGHT; GRAHAM I.H. KERLEY (Conservation Biology, 2006)
A major challenge for conservation assessments is to identify priority areas that incorporate biological patterns and processes. Because large‐scale processes are mostly oriented along environmental gradients, we propose to accommodate them by designing regional‐scale corridors to capture these gradients. Based on systematic conservation planning principles such as representation and persistence, we identified large tracts of untransformed land (i.e., conservation corridors) for conservation that would achieve biodiversity targets for pattern and process in the Subtropical Thicket Biome of South Africa. We combined least‐cost path analysis with a target‐driven algorithm to identify the best option for capturing key environmental gradients while considering biodiversity targets and conservation opportunities and constraints. We identified seven conservation corridors on the basis of subtropical thicket representation, habitat transformation and degradation, wildlife suitability, irreplaceability of vegetation types, protected area networks, and future land‐use pressures. These conservation corridors covered 21.1% of the planning region (ranging from 600 to 5200 km 2 ) and successfully achieved targets for biological processes and to a lesser extent for vegetation types. The corridors we identified are intended to promote the persistence of ecological processes (gradients and fixed processes) and fulfill half of the biodiversity pattern target. We compared the conservation corridors with a simplified corridor design consisting of a fixed‐width buffer along major rivers. Conservation corridors outperformed river buffers in seven out of eight criteria. Our corridor design can provide a tool for quantifying trade‐offs between various criteria (biodiversity pattern and process, implementation constraints and opportunities). A land‐use management model was developed to facilitate implementation of conservation actions within these corridors.

Antagonistic effects of seed dispersal and herbivory on plant migration - Mark Vellend; Tiffany M. Knight; John M. Drake (Ecology Letters, 2006)
The two factors that determine plant migration rates – seed dispersal and population growth – are generally treated independently, despite the fact that many animals simultaneously enhance plant migration rate via seed dispersal, and decrease it via negative effects of herbivory on population growth. Using extensive empirical data, we modelled the antagonistic effects of seed dispersal and herbivory by white‐tailed deer on potential migration rates of Trillium grandiflorum , a forest herb in eastern North America. This novel antagonistic interaction is illustrated by maximum migration rates occurring at intermediate, but low herbivory (

Assessing Conservation Management's Evidence Base: a Survey of Management‐Plan Compilers in the United Kingdom and Australia - ANDREW S. PULLIN; TERI M. KNIGHT (Conservation Biology, 2005)
Conservation management is becoming increasingly resource intensive as threats to biodiversity grow through habitat destruction, habitat disturbance, and overexploitation. To achieve successful conservation and sustainable use of natural resources, we need to scientifically evaluate the effectiveness of conservation interventions and provide an efficient framework through which scientific evidence can be used to support decision making in policy and practice. We conducted the first formal assessment of the extent to which scientific evidence is used in conservation management through a questionnaire survey and follow‐up interviews of compilers of protected‐area management plans from major conservation organizations within the United Kingdom and Australia. Our survey results show that scientific information is not being used systematically to support decision making largely because it is not easily accessible to decision makers. This, in combination with limited monitoring and evaluation of effectiveness of management interventions, results in the majority of decisions being based on experience rather than on evidence. To address this problem we propose using an evidence‐based framework adapted from that used in the health services and explain how we are currently putting an equivalent framework into practice by establishing review and dissemination units to serve the conservation sector.

Survival of Penicillium bilaiae inoculated on canola seed treated with Vitavax RS and Extender - Erin M. Burton; J. D. Knight (Biology and Fertility of Soils, 2005)

Directed Gp130-Mediated Signaling Dissociates Inflammation from Fibrosis in Bleomycin Induced Lung Injury - R. J. J. O’Donoghue; G. P. Anderson; S. Bozinovski; J. Jones; M. Ernst; D. A. Knight; S. E. Mutsaers (Inflammation Research, 2005)

Policy needs to improve marine capture fisheries management and to define a role for marine protected areas in Indonesia - P. J. MOUS; J. S. PET; Z. ARIFIN; R. DJOHANI; M. V. ERDMANN; A. HALIM; M. KNIGHT; L. PET‐SOEDE; G. WIADNYA (Fisheries Management and Ecology, 2005)
Management of Indonesia's marine capture fisheries faces a huge dilemma: evidence suggests that most, if not all, of Indonesia's capture fisheries are fully or overexploited, but the fishery sector is still expected to contribute to the increase of Indonesia's gross national product (GNP) through an increase in total catches. Furthermore, the current practice of using catch‐effort data and Maximum Sustainable Yield (MSY) models to inform Indonesia's fisheries policies is flawed, putting sustainability and long‐term profitability of Indonesia's fisheries at risk. It is argued that the following shift in capture fisheries management policy must be achieved to ensure the survival of Indonesia's fish stocks and fisheries: 1 a shift in fisheries policy from development‐oriented management towards management for sustainability; 2 acceptance by fisheries managers that ‘untapped resources’ may not exist or cannot be exploited profitably; 3 acceptance by fisheries managers that any transfer of fishing effort between fishing grounds may contribute to collapse of local fisheries; 4 a shift in fisheries management from MSY models to eco‐system based management, wherein Marine Protected Areas should play an important role.

Will loss of snow cover during climatic warming expose New Zealand alpine plants to increased frost damage? - Peter Bannister; Tanja Maegli; Katharine J. M. Dickinson; Stephan R. P. Halloy; Allison Knight; Janice M. Lord; Alan F. Mark; Katrina L. Spencer (Oecologia, 2005)

Delineating species for conservation using mitochondrial sequence data: the taxonomic status of two problematic Bombus species (Hymenoptera: Apidae) - J. S. Ellis; M. E. Knight; D. Goulson (Journal of Insect Conservation, 2005)

An interspecific comparison of foraging range and nest density of four bumblebee ( Bombus ) species - M. E. KNIGHT; A. P. MARTIN; S. BISHOP; J. L. OSBORNE; R. J. HALE; R. A. SANDERSON; D. GOULSON (Molecular Ecology, 2005)
Bumblebees are major pollinators of crops and wildflowers in northern temperate regions. Knowledge of their ecology is vital for the design of effective management and conservation strategies but key aspects remain poorly understood. Here we employed microsatellite markers to estimate and compare foraging range and nest density among four UK species: Bombus terrestris, Bombus pascuorum, Bombus lapidarius , and Bombus pratorum . Workers were sampled along a 1.5‐km linear transect across arable farmland. Eight or nine polymorphic microsatellite markers were then used to identify putative sisters. In accordance with previous studies, minimum estimated maximum foraging range was greatest for B. terrestris (758 m) and least for B. pascuorum (449 m). The estimate for B. lapidarius was similar to B. pascuorum (450 m), while that of B. pratorum was intermediate (674 m). Since the area of forage available to bees increases as the square of foraging range, these differences correspond to a threefold variation in the area used by bumblebee nests of different species. Possible explanations for these differences are discussed. Estimates for nest density at the times of sampling were 29, 68, 117, and 26/km 2 for B. terrestris, B. pascuorum, B. lapidarius and B. pratorum , respectively. These data suggest that even among the most common British bumblebee species, significant differences in fundamental aspects of their ecology exist, a finding that should be reflected in management and conservation strategies.

Nonequilibrium conditions following landscape rearrangement: the relative contribution of past and current hydrological landscapes on the genetic structure of a stream‐dwelling fish - JOCELYN POISSANT; THOMAS W. KNIGHT; MOIRA M. FERGUSON (Molecular Ecology, 2005)
Interpreting patterns of population structure in nature is often challenging, especially in dynamic landscapes where population genetic connectivity evolves over time. In this study, we document the absence of migration‐drift equilibrium in a stream‐dwelling euryhaline fish resulting from past fine‐scale drainage rearrangements and evaluate the relative contribution of past and current hydrological landscapes on observed population structure. Based on allelic variation at nine microsatellite loci, genetic relationships among 12 populations of brook charr, Salvelinus fontinalis , from Gros Morne National Park of Canada (GMNP, Newfoundland, Canada) did not reflect current stream hierarchical structure. In addition, we observed no correlation between population differentiation and contemporary landscape features (waterway distance and sums of altitudinal differences). Instead, population relationships were consistent with historical hydrological structure predicted a priori based on geomorphological and biogeographical evidences. Also, population differentiation was strongly correlated with inferred historical landscape features. Contemporary barriers have apparently preserved the signature of past genetic connectivity by constraining gene flow. Based on the relationships between population differentiation and current and past landscape features at various spatial scales, we suggest that brook charr genetic diversity in GMNP is mostly the result of small distance migrations at the time of colonization and subsequent differentiation through drift. This study highlights the potential of approaching landscapes from a combination of contemporary and historical perspectives when interpreting nonequilibrium population structures resulting from landscape rearrangement.

The role of hydrogen bonding in the thermal expansion and dehydration of brushite, di-calcium phosphate dihydrate - P. F. Schofield; K. S. Knight; J. A. M. van der Houwen; E. Valsami-Jones (Physics and Chemistry of Minerals, 2004)

Nature Conservation Requires More than a Passion for Species - RICHARD M. COWLING; ANDREW T. KNIGHT; DANIEL P. FAITH; SIMON FERRIER; AMANDA T. LOMBARD; AMANDA DRIVER; MATHIEU ROUGET; KRISTAL MAZE; PHILIP G. DESMET (Conservation Biology, 2004)

Differences in sounds made by courting males of three closely related Lake Malawi cichlid species - M. C. P. Amorim; M. E. Knight; Y. Stratoudakis; G. F. Turner (Journal of Fish Biology, 2004)
Courtship sounds made by three sympatric cichlid species, Pseudotropheus zebra , P. callainos and an undescribed species known as P . ‘zebra gold’ were recorded and compared to investigate the potential role of acoustic signals in mate choice. Sounds were emitted during ‘quiver’ and ‘circle’ components of the male courtship display and consisted of rapidly repeated pulse units. Some sound variables differed significantly among species with P. callainos generally being separated from the other two species. This species produced sounds with higher peak frequency (for a given length) and lower number of pulses than P . ‘zebra gold’ and higher pulse durations than P. zebra . In addition, standard length was inversely related to peak frequency in both P . ‘zebra gold’ and P. callainos (this relation was not tested in P. zebra due to the small sample size). These differences might indicate different regimes of intraspecific sexual selection among the three species.

Homologues of the maize rust resistance gene Rp1-D are genetically associated with a major rust resistance QTL in sorghum - C. L. McIntyre; S. M. Hermann; R. E. Casu; D. Knight; J. Drenth; Y. Tao; S. M. Brumbley; I. D. Godwin; S. Williams; G. R. Smith; J. M. Manners (Theoretical and Applied Genetics, 2004)

Confocal Analysis of Local and Cellular Strains in Chondrocyte-Agarose Constructs Subjected to Mechanical Shear - Yoshinori Sawae; Julia C. Shelton; Dan L. Bader; Martin M. Knight (Annals of Biomedical Engineering, 2004)

Tidal currents, energy flux and bottom boundary layer thickness in the Clyde Sea and North Channel of the Irish Sea - A. M. Davies; P. Hall; M. J. Howarth; P. J. Knight; R. J. Player (Ocean Dynamics, 2004)

Survival and Growth of Hyalella azteca Exposed to Three Mississippi Oxbow Lake Sediments - M. T. Moore; R. E. Lizotte; C. M. Cooper; S. Smith; S. S. Knight (Bulletin of Environmental Contamination and Toxicology, 2004)

Floral density, pollen limitation, and reproductive success in Trillium grandiflorum - Tiffany M. Knight (Oecologia, 2003)

Stochastic estimation of facies using ground penetrating radar data - S. Moysey; J. Caers; R. Knight; R. M. Allen-King (Stochastic Environmental Research and Risk Assessment, 2003)

Drought‐induced mosquito outbreaks in wetlands - Jonathan M. Chase; Tiffany M. Knight (Ecology Letters, 2003)
Mosquitoes are not only a nuisance, but also vector many important human and animal diseases. Here, in opposition with the dogma that increased precipitation predicts mosquito abundance, we hypothesize that mosquitoes should show population outbreaks after drought years. Specifically, we suggest that in wetlands that never dry (permanent), predators limit mosquito abundance, whereas in wetlands that dry yearly (temporary), competitors that are well adapted to predictable drying, limit mosquito abundance. However, in wetlands that dry only during drought years (semi‐permanent), mosquito predators and competitors are eliminated and must recolonize following a drought, and the abundance of wetland mosquitoes can skyrocket. We present supportive evidence for this hypothesis from surveys of natural wetlands and from a controlled mesocosm experiment. We conclude that this framework may provide a reliable way to predict and prepare for year‐to‐year variation in mosquito abundances at large spatial scales.

Soil‐surface carbon dioxide efflux and microbial biomass in relation to tree density 13 years after a stand replacing fire in a lodgepole pine ecosystem - CREIGHTON M. LITTON; MICHAEL G. RYAN; DENNIS H. KNIGHT; PETER D. STAHL (Global Change Biology, 2003)
The effects of fire on soil‐surface carbon dioxide (CO 2 ) efflux, F S , and microbial biomass carbon, C mic , were studied in a wildland setting by examining 13‐year‐old postfire stands of lodgepole pine differing in tree density ( 500 000 trees ha −1 ) in Yellowstone National Park (YNP). In addition, young stands were compared to mature lodgepole pine stands (∼110‐year‐old) in order to estimate ecosystem recovery 13 years after a stand replacing fire. Growing season F S increased with tree density in young stands (1.0 µmol CO 2 m −2 s −1 in low‐density stands, 1.8 µmol CO 2 m −2 s −1 in moderate‐density stands and 2.1 µmol CO 2 m −2 s −1 in high‐density stands) and with stand age (2.7 µmol CO 2 m −2 s −1 in mature stands). Microbial biomass carbon in young stands did not differ with tree density and ranged from 0.2 to 0.5 mg C g −1 dry soil over the growing season; C mic was significantly greater in mature stands (0.5–0.8 mg C g −1 dry soil). Soil‐surface CO 2 efflux in young stands was correlated with biotic variables (above‐ground, below‐ground and microbial biomass), but not with abiotic variables (litter and mineral soil C and N content, bulk density and soil texture). Microbial biomass carbon was correlated with below‐ground plant biomass and not with soil carbon and nitrogen, indicating that plant activity controls not only root respiration, but C mic pools and overall F S rates as well. These findings support recent studies that have demonstrated the prevailing importance of plants in controlling rates of F S and suggest that decomposition of older, recalcitrant soil C pools in this ecosystem is relatively unimportant 13 years after a stand replacing fire. Our results also indicate that realistic predictions and modeling of terrestrial C cycling must account for the variability in tree density and stand age that exists across the landscape as a result of natural disturbances.

Construction and integration of radiation-hybrid and cytogenetic maps of dog Chromosome X - Helen F. Spriggs; Nigel G. Holmes; Matthew Breen; Panos Deloukas; Cordelia F. Langford; Mark T. Ross; Nigel P. Carter; Maria E. Davis; Catherine Knights; Angela Smith; Christine J. Farr; Linda C. McCarthy; et al. (Mammalian Genome, 2003)

Sulphation of the salivary mucin MG1 (MUC-5B) is not correlated to the degree of its sialylation and is unaffected by cystic fibrosis - Shori D.; Hansen J.; Kalogeridis A.; Kariyawasam H.; Genter T.; Koch C.; Knight R.; Hodson M. (Pflügers Archiv - European Journal of Physiology, 2001)

Altered sialyl- and fucosyl-linkage on mucins in cystic fibrosis patients promotes formation of the sialyl-Lewis X determinant on salivary MUC-5B and MUC-7 - Shori D.; Genter T.; Hansen J.; Koch C.; Wyatt H.; Kariyawasam H.; Knight R.; Hodson M.; Kalogeridis A.; Tsanakas I. (Pflügers Archiv - European Journal of Physiology, 2001)

A pear-derived kairomone with pheromonal potency that attracts male and female codling moth, Cydia pomonella (L.) - Douglas M. Light; Alan L. Knight; Clive A. Henrick; Dayananda Rajapaska; Bill Lingren; Joseph C. Dickens; Katherine M. Reynolds; Ronald G. Buttery; Gloria Merrill; James Roitman; Bruce C. Campbell (The Science of Nature, 2001)

Attractants from Bartlett pear for codling moth, Cydia pomonella (L.), larvae - Alan L. Knight; Douglas M. Light (The Science of Nature, 2001)

Temporal changes in cytoskeletal organisation within isolated chondrocytes quantified using a novel image analysis technique - M. M. Knight; B. D. Idowu; D. A. Lee; D. L. Bader (Medical & Biological Engineering & Computing, 2001)

Isolation and characterisation of a full-length genomic clone encoding a plastidic glucose 6-phosphate dehydrogenase from Nicotiana tabacum - Jacqueline S. Knight; Michael J. Emes; Phillip M. Debnam (Planta, 2001)

Compressive Deformation and Damage of Muscle Cell Subpopulations in a Model System - Carlijn V. C. Bouten; Martin M. Knight; David A. Lee; Daniel L. Bader (Annals of Biomedical Engineering, 2001)

Effectiveness in Conservation Practice: Pointers from Medicine and Public Health - Andrew S. Pullin; Teri M. Knight (Conservation Biology, 2001)
Practical conservation activity is increasing globally and is being undertaken by many different government and nongovernmental organizations. In the majority of cases, justification for proposed actions is experience‐based rather than evidence‐based, action is often taken without monitoring or evaluation of effectiveness, and results are rarely widely disseminated. Conservation has been compared with medicine as a crisis discipline in which action is often required urgently in the absence of good information. The practice of medicine has recently gone through an effectiveness revolution that has improved the criteria upon which treatment strategies are based by progressing from reliance on personal experience to reliance on scientific evidence. We draw parallels between medicine and conservation and present a practical framework to encourage evidence‐based conservation action. Our rationale is that conservation actions for which scarce resources are sought should be justified by good scientific evidence. In our view this will also encourage more research addressing practical issues in conservation management.

Effectiveness in Conservation Practice: Pointers from Medicine and Public Health - Andrew S. Pullin; Teri M. Knight (Conservation Biology, 2001)

Octahedral cation ordering in olivine at high temperature. II: an in situ neutron powder diffraction study on synthetic MgFeSiO 4 (Fa50) - S. A. T. Redfern; G. Artioli; R. Rinaldi; C. M. B. Henderson; K. S. Knight; B. J. Wood (Physics and Chemistry of Minerals, 2000)

Two Cases of Pulmonary Complications Associated with a Recently Recognised Salmonella enteritidis Phage Type, 21b, Affecting Immunocompetent Adults - J. C. Knight; M. Knight; M. J. Smith (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

G130V, a common FRDA point mutation, appears to have arisen from a common founder - M.B. Delatycki; M. Knight; M. Koenig; M. Cossée; R. Williamson; S.M. Forrest (Human Genetics, 1999)

G130V, a common FRDA point mutation, appears to have arisen from a common founder - M.B. Delatycki; M. Knight; M. Koenig; M. Cossée; R. Williamson; S.M. Forrest (Human Genetics, 1999)

Evidence for male‐biased dispersal in Lake Malawi cichlids from microsatellites - M. E. Knight; M. J. H. van Oppen; H. L. Smith; C. Rico; G. M. Hewitt; G. F. Turner (Molecular Ecology, 1999)
This study addressed within‐population dispersal patterns among the species‐rich Lake Malawi cichlids, specifically among the rock‐dwelling mbuna group. Relatedness values were calculated for 160 individuals belonging to two species from known locations in the field by screening six highly polymorphic microsatellite loci. The results from both species indicate that spatially adjacent females have higher average relatedness values than those separated by larger distances, but that this pattern is reversed in males. This therefore provides firm evidence for male‐biased dispersal within the Malawian cichlid flock.

Changes in the Probability of Heavy Precipitation: Important Indicators of Climatic Change - Pavel Ya. Groisman; Thomas R. Karl; David R. Easterling; Richard W. Knight; Paul F. Jamason; Kevin J. Hennessy; Ramasamy Suppiah; Cher M. Page; Joanna Wibig; Krzysztof Fortuniak; Vyacheslav N. Razuvaev; Arthur Douglas; et al. (Climatic Change, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

The Use of Bioassays and Toxicity Identification Evaluation (TIE) Procedures to Assess Recovery and Effectiveness of Remedial Activities in a Mine Drainage-Impacted Stream System - L. Deanovic; V. M. Connor; A. W. Knight; K. J. Maier (Archives of Environmental Contamination and Toxicology, 1999)

Enhancing immigration and recruitment of eels: the use of passes and associated trapping systems - B. KNIGHTS; E. M. WHITE (Fisheries Management and Ecology, 1998)
Immigration of catadromous anguillid eels into fresh water can be impeded by barriers such as barrages, weirs and dams. The uses of passes and trap‐and‐transport systems to enhance recruitment are reviewed. Pre‐construction studies of the needs for passes and traps are discussed in relation to key biological and hydraulic management criteria. Recommendations for pass and trap designs and placement are made in the context of site‐specific biotic and abiotic factors. Reference is made to experience gained from eel passes and trapping systems in use throughout the world, and to experimental and pre‐and post‐construction monitoring studies. Practical recommendations are made for the design and use of eel passes and traps for monitoring studies and for trap‐and‐transport stocking.

Microsatellite paternity analysis on captive Lake Malawi cichlids supports reproductive isolation by direct mate choice - M. E. KNIGHT; G. F. TURNER; C. RICO; M. J. H. VAN OPPEN; G. M. HEWITT (Molecular Ecology, 1998)
Three sympatrically occurring members of a cichlid fish species complex from Lake Malawi have previously been reported to show assortative mating in the field. Offspring from three experimental tanks each housing both sexes of all three members of this complex were screened at one to four microsatellite loci to determine paternity. Reproductive isolation was found to persist without exception under laboratory conditions, providing strong evidence for behavioural barriers to mating. Direct mate choice is suggested as the process preventing interbreeding. The results are interpreted with reference to the rapid and explosive evolution of the cichlid group.

Rehabilitation of aquatic habitats in warmwater streams damaged by channel incision in Mississippi - F. D. Shields; S. S. Knight; C. M. Cooper (Hydrobiologia, 1998)

Dynamics of upstream migration of the European eel, Anguilla anguilla (L.), in the Rivers Severn and Avon, England, with special reference to the effects of man‐made barriers - E. M. WHITE; B. KNIGHTS (Fisheries Management and Ecology, 1997)
The upstream migration of European eels, Anguilla anguilla (L.), was studied during 1991–1993 in the Rivers Severn and Avon using traps mounted on weir or sluice barriers. Only pigmented elvers and juvenile eels were trapped at the tidal limits, catches being equivalent to about 0.8% of the commercial glass eel catch in the lower estuary. First catches were made as temperatures rose above 10–11 °C. Pigmentation‐stage analyses and body size data indicated that estuarine migration was slow and that natural mortality was probably very high. Relatively more eels were trapped in the Severn compared with the Avon, but in both rivers the number of immigrants decreased rapidly upstream of the tidal limits, whilst the average size and age increased. The number and severity of weir and sluice barriers to be surmounted exerted a greater effect than distance alone. Recapture rates of marked eels were low (1–2%), implying variable migratory tendencies and/or high mortality. Mean migration rate in the non‐tidal rivers was 0.64 ± 0.6 km day –1 and some eels were not recaptured until one or two years after release. Speed of migration increased with temperatures above 15–16 °C. Relationships between migration dynamics, barriers and the scarcity of upriver stocks of eels and distorted population structures in the two rivers are discussed. Recommendations are made for the provision of passes and/or stocking to enhance migration and recruitment.

Environmental factors affecting migration of the European eel in the Rivers Severn and Avon, England - E. M. White; B. Knights (Journal of Fish Biology, 1997)
Studies were conducted during 1991–1993 on environmental factors affecting the upstream migration of eels in the Rivers Severn and Avon, England. Migrants (> 156 000 pigmented elvers and > 189 000 juveniles) were trapped as they attempted to ascend weir or sluice barriers. Multiple regression models were developed to compare catches per trap per night (C) with data for various key environmental parameters at seven sites, from the tidal limit to a maximum of 42.5 km upstream. The key stimulus for migration of both elvers and juveniles at the tidal limit was water temperature, with some weaker monthly influences related to seasonal temperature increases. Smaller annual influences probably related to earlier glass eel recruitment into the lower estuary. A weak early tidal effect was demonstrated only once, in 1993 in the Severn. Temperature also exerted significant effects on C of juvenile eels at the tidal limit and in the non‐tidal rivers, although effects weakened with distance upstream. Year, month, river flows and whether traps were mounted on weirs or sluices made only small contributions at a few sites. Distance between traps also contributed to combined data for upper Severn sites. The threshold temperature in all cases was 14–16°C, with low to zero catches below 10–11°C, catch maxima being achieved above 18–20°C. The implications of strong temperature‐dependence of migration in relation to stock recruitment and management are discussed. Special reference is made to recent decreases in recruitment of eels to Europe and N. America and possible long‐term effects of global warming.

Association Business - David Curwen; Ronald Knight; Therese M. Work; Hugh J. Murphy; Pete Weingartner; John Ojala; Gary Franc; Roger Brook; Tom German; Sam Thorton; John Bamberg; John C. Wallace; et al. (American Journal of Potato Research, 1993)

The amplitudes of unit events in Limulus photoreceptors are modulated from an input that resembles the overall response - Norberto M. Grzywacz; Peter Hillman; Bruce W. Knight (Biological Cybernetics, 1992)

Response transfer functions of Limulus ventral photoreceptors: interpretation in terms of transduction mechanisms - Norberto M. Grzywacz; Peter Hillman; Bruce W. Knight (Biological Cybernetics, 1992)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

PAA Annual Reports Report of the Treasurer (1988–1989) - Therese M. Work; Pete Weingartner; Hugh J. Murphy; Ronald Knight Business; Lind Sanford; Linda Best; Florian I. Lauer; Joe Pavek; Shelley Jansky; James Bryan; M. D. Groskopp; Charles R. Brown; et al. (American Journal of Potato Research, 1989)

Variation in ten lysosomal hydrolase enzyme activities in inbred mouse strains - William G. Johnson; Jacqueline L. Hong; Susan M. Knights (Biochemical Genetics, 1986)

Evaluation of the gas transfer characteristics of porous copolyurethane oxygenator membranes - P. M. Knight; D. J. Lyman (Annals of Biomedical Engineering, 1985)

Metabolic regulation in Pseudomonas oxalaticus OX1 - M. Knight; L. Dijkhuizen; W. Harder (Archives of Microbiology, 1978)

Metabolic regulation in Pseudomonas oxalaticus OX1 - L. Dijkhuizen; M. Knight; W. Harder (Archives of Microbiology, 1978)

Effects of leached mirex on experimental communities of estuarine animals - M. E. Tagatz; P. W. Borthwick; J. M. Ivey; J. Knight (Archives of Environmental Contamination and Toxicology, 1976)

Incorporation of amino acids into protein by cell-free extracts of penicillium chrysogenum - C. W. Haidle; J. M. Kornfeld; S. G. Knight (Archives of Microbiology, 1966)

Attenuated strains of the virus of foot-and-mouth disease. Studies in small animals with strains of common origin modified by different methods - H. H. Skinner; I. M. Smith; Susan E. Hollom; E. H. Knight (Archives of Virology, 1963)